Apical contacts stemming from incomplete delamination guide progenitor cell allocation through a dragging mechanism - Pulgar, Eduardo; Schwayer, Cornelia; Guerrero, Néstor; López, Loreto; Márquez, Susana; Härtel, Steffen; Soto, Rodrigo; Heisenberg, Carl Philipp; Concha, Miguel L. (eLife)
The developmental strategies used by progenitor cells to endure a safe journey from their induction place towards the site of terminal differentiation are still poorly understood. Here we uncovered a progenitor cell allocation mechanism that stems from an incomplete process of epithelial delamination that allows progenitors to coordinate their movement with adjacent extra-embryonic tissues. Progenitors of the zebrafish laterality organ originate from the surface epithelial enveloping layer by an apical constriction process of cell delamination. During this process, progenitors retain long-term apical contacts that enable the epithelial layer to pull a subset of progenitors along their way towards the vegetal pole. The remaining delaminated progenitors follow apically-attached progenitors’ movement by a co-attraction mechanism, avoiding sequestration by the adjacent endoderm, ensuring their fate and collective allocation at the differentiation site. Thus, we reveal that incomplete delamination serves as a cellular platform for coordinated tissue movements during development. Impact Statement: Incomplete delamination serves as a cellular platform for coordinated tissue movements during development, guiding newly formed progenitor cell groups to the differentiation site.
Keywords: cell delamination; apical constriction; dragging; mechanical forces; collective 18 locomotion; dorsal forerunner cells; zebrafish

Symbolic time and space tradeoffs for probabilistic verification - Chatterjee, Krishnendu; Dvorak, Wolfgang; Henzinger, Monika H; Svozil, Alexander (Proceedings of the 36th Annual ACM/IEEE Symposium on Logic in Computer Science)
We present a faster symbolic algorithm for the following central problem in probabilistic verification: Compute the maximal end-component (MEC) decomposition of Markov decision processes (MDPs). This problem generalizes the SCC decomposition problem of graphs and closed recurrent sets of Markov chains. The model of symbolic algorithms is widely used in formal verification and model-checking, where access to the input model is restricted to only symbolic operations (e.g., basic set operations and computation of one-step neighborhood). For an input MDP with n vertices and m edges, the classical symbolic algorithm from the 1990s for the MEC decomposition requires O(n2) symbolic operations and O(1) symbolic space. The only other symbolic algorithm for the MEC decomposition requires O(nm−−√) symbolic operations and O(m−−√) symbolic space. A main open question is whether the worst-case O(n2) bound for symbolic operations can be beaten. We present a symbolic algorithm that requires O˜(n1.5) symbolic operations and O˜(n−−√) symbolic space. Moreover, the parametrization of our algorithm provides a trade-off between symbolic operations and symbolic space: for all 0<ϵ≤1/2 the symbolic algorithm requires O˜(n2−ϵ) symbolic operations and O˜(nϵ) symbolic space ( O˜ hides poly-logarithmic factors). Using our techniques we present faster algorithms for computing the almost-sure winning regions of ω -regular objectives for MDPs. We consider the canonical parity objectives for ω -regular objectives, and for parity objectives with d -priorities we present an algorithm that computes the almost-sure winning region with O˜(n2−ϵ) symbolic operations and O˜(nϵ) symbolic space, for all 0<ϵ≤1/2 .
Keywords: Computer science; Computational modeling; Markov processes; Probabilistic logic; Formal verification; Game Theory

Hydrodynamics for the partial exclusion process in random environment - Floreani, Simone; Redig, Frank; Sau, Federico (Stochastic Processes and their Applications)
In this paper, we introduce a random environment for the exclusion process in obtained by assigning a maximal occupancy to each site. This maximal occupancy is allowed to randomly vary among sites, and partial exclusion occurs. Under the assumption of ergodicity under translation and uniform ellipticity of the environment, we derive a quenched hydrodynamic limit in path space by strengthening the mild solution approach initiated in Nagy (2002) and Faggionato (2007). To this purpose, we prove, employing the technology developed for the random conductance model, a homogenization result in the form of an arbitrary starting point quenched invariance principle for a single particle in the same environment, which is a result of independent interest. The self-duality property of the partial exclusion process allows us to transfer this homogenization result to the particle system and, then, apply the tightness criterion in Redig et al. (2020).
Keywords: hydrodynamic limit; random environment; random conductance model; arbitrary starting point quenched invariance principle; duality; mild solution

Stochastic processes with expected stopping time - Chatterjee, Krishnendu; Doyen, Laurent (Proceedings of the 36th Annual ACM/IEEE Symposium on Logic in Computer Science)
Markov chains are the de facto finite-state model for stochastic dynamical systems, and Markov decision processes (MDPs) extend Markov chains by incorporating non-deterministic behaviors. Given an MDP and rewards on states, a classical optimization criterion is the maximal expected total reward where the MDP stops after T steps, which can be computed by a simple dynamic programming algorithm. We consider a natural generalization of the problem where the stopping times can be chosen according to a probability distribution, such that the expected stopping time is T, to optimize the expected total reward. Quite surprisingly we establish inter-reducibility of the expected stopping-time problem for Markov chains with the Positivity problem (which is related to the well-known Skolem problem), for which establishing either decidability or undecidability would be a major breakthrough. Given the hardness of the exact problem, we consider the approximate version of the problem: we show that it can be solved in exponential time for Markov chains and in exponential space for MDPs.
Keywords: Computer science; Heuristic algorithms; Memory management; Automata; Markov processes; Probability distribution; Complexity theory

Parallelism versus latency in simplified successive-cancellation decoding of polar codes - Hashemi, Seyyed Ali; Mondelli, Marco; Fazeli, Arman; Vardy, Alexander; Cioffi, John; Goldsmith, Andrea (2021 IEEE International Symposium on Information Theory)
This paper characterizes the latency of the simplified successive-cancellation (SSC) decoding scheme for polar codes under hardware resource constraints. In particular, when the number of processing elements P that can perform SSC decoding operations in parallel is limited, as is the case in practice, the latency of SSC decoding is O(N1−1 μ+NPlog2log2NP), where N is the block length of the code and μ is the scaling exponent of polar codes for the channel. Three direct consequences of this bound are presented. First, in a fully-parallel implementation where P=N2 , the latency of SSC decoding is O(N1−1/μ) , which is sublinear in the block length. This recovers a result from an earlier work. Second, in a fully-serial implementation where P=1 , the latency of SSC decoding scales as O(Nlog2log2N) . The multiplicative constant is also calculated: we show that the latency of SSC decoding when P=1 is given by (2+o(1))Nlog2log2N . Third, in a semi-parallel implementation, the smallest P that gives the same latency as that of the fully-parallel implementation is P=N1/μ . The tightness of our bound on SSC decoding latency and the applicability of the foregoing results is validated through extensive simulations.

The Atiyah-Bott formula and connectivity in chiral Koszul duality - Ho, Quoc P (Advances in Mathematics)
The ⊗*-monoidal structure on the category of sheaves on the Ran space is not pro-nilpotent in the sense of [3]. However, under some connectivity assumptions, we prove that Koszul duality induces an equivalence of categories and that this equivalence behaves nicely with respect to Verdier duality on the Ran space and integrating along the Ran space, i.e. taking factorization homology. Based on ideas sketched in [4], we show that these results also offer a simpler alternative to one of the two main steps in the proof of the Atiyah-Bott formula given in [7] and [5].
Keywords: Chiral algebras; Chiral homology; Factorization algebras; Koszul duality; Ran space

RIM-binding protein 2 organizes Ca21 channel topography and regulates release probability and vesicle replenishment at a fast central synapse - Butola, Tanvi; Alvanos, Theocharis; Hintze, Anika; Koppensteiner, Peter; Kleindienst, David; Shigemoto, Ryuichi; Wichmann, Carolin; Moser, Tobias (Journal of Neuroscience)
Rab-interacting molecule (RIM)-binding protein 2 (BP2) is a multidomain protein of the presynaptic active zone (AZ). By binding to RIM, bassoon (Bsn), and voltage-gated Ca2+ channels (CaV), it is considered to be a central organizer of the topography of CaV and release sites of synaptic vesicles (SVs) at the AZ. Here, we used RIM-BP2 knock-out (KO) mice and their wild-type (WT) littermates of either sex to investigate the role of RIM-BP2 at the endbulb of Held synapse of auditory nerve fibers (ANFs) with bushy cells (BCs) of the cochlear nucleus, a fast relay of the auditory pathway with high release probability. Disruption of RIM-BP2 lowered release probability altering short-term plasticity and reduced evoked EPSCs. Analysis of SV pool dynamics during high-frequency train stimulation indicated a reduction of SVs with high release probability but an overall normal size of the readily releasable SV pool (RRP). The Ca2+-dependent fast component of SV replenishment after RRP depletion was slowed. Ultrastructural analysis by superresolution light and electron microscopy revealed an impaired topography of presynaptic CaV and a reduction of docked and membrane-proximal SVs at the AZ. We conclude that RIM-BP2 organizes the topography of CaV, and promotes SV tethering and docking. This way RIM-BP2 is critical for establishing a high initial release probability as required to reliably signal sound onset information that we found to be degraded in BCs of RIM-BP2-deficient mice in vivo. SIGNIFICANCE STATEMENT: Rab-interacting molecule (RIM)-binding proteins (BPs) are key organizers of the active zone (AZ). Using a multidisciplinary approach to the calyceal endbulb of Held synapse that transmits auditory information at rates of up to hundreds of Hertz with submillisecond precision we demonstrate a requirement for RIM-BP2 for normal auditory signaling. Endbulb synapses lacking RIM-BP2 show a reduced release probability despite normal whole-terminal Ca2+ influx and abundance of the key priming protein Munc13-1, a reduced rate of SV replenishment, as well as an altered topography of voltage-gated (CaV)2.1 Ca2+ channels, and fewer docked and membrane proximal synaptic vesicles (SVs). This hampers transmission of sound onset information likely affecting downstream neural computations such as of sound localization.

A Ramsey theorem for finite monoids - Jecker, Ismael R (38th International Symposium on Theoretical Aspects of Computer Science)
Repeated idempotent elements are commonly used to characterise iterable behaviours in abstract models of computation. Therefore, given a monoid M, it is natural to ask how long a sequence of elements of M needs to be to ensure the presence of consecutive idempotent factors. This question is formalised through the notion of the Ramsey function R_M associated to M, obtained by mapping every k ∈ ℕ to the minimal integer R_M(k) such that every word u ∈ M^* of length R_M(k) contains k consecutive non-empty factors that correspond to the same idempotent element of M. In this work, we study the behaviour of the Ramsey function R_M by investigating the regular 𝒟-length of M, defined as the largest size L(M) of a submonoid of M isomorphic to the set of natural numbers {1,2, …, L(M)} equipped with the max operation. We show that the regular 𝒟-length of M determines the degree of R_M, by proving that k^L(M) ≤ R_M(k) ≤ (k|M|⁴)^L(M). To allow applications of this result, we provide the value of the regular 𝒟-length of diverse monoids. In particular, we prove that the full monoid of n × n Boolean matrices, which is used to express transition monoids of non-deterministic automata, has a regular 𝒟-length of (n²+n+2)/2.

Postpartum hemorrhage risk is driven by changes in blood composition through pregnancy - Robinson, Matthew Richard; Patxot, Marion; Stojanov, Miloš; Blum, Sabine; Baud, David (Scientific Reports)
The extent to which women differ in the course of blood cell counts throughout pregnancy, and the importance of these changes to pregnancy outcomes has not been well defined. Here, we develop a series of statistical analyses of repeated measures data to reveal the degree to which women differ in the course of pregnancy, predict the changes that occur, and determine the importance of these changes for post-partum hemorrhage (PPH) which is one of the leading causes of maternal mortality. We present a prospective cohort of 4082 births recorded at the University Hospital, Lausanne, Switzerland between 2009 and 2014 where full labour records could be obtained, along with complete blood count data taken at hospital admission. We find significant differences, at a [Formula: see text] level, among women in how blood count values change through pregnancy for mean corpuscular hemoglobin, mean corpuscular volume, mean platelet volume, platelet count and red cell distribution width. We find evidence that almost all complete blood count values show trimester-specific associations with PPH. For example, high platelet count (OR 1.20, 95% CI 1.01-1.53), high mean platelet volume (OR 1.58, 95% CI 1.04-2.08), and high erythrocyte levels (OR 1.36, 95% CI 1.01-1.57) in trimester 1 increased PPH, but high values in trimester 3 decreased PPH risk (OR 0.85, 0.79, 0.67 respectively). We show that differences among women in the course of blood cell counts throughout pregnancy have an important role in shaping pregnancy outcome and tracking blood count value changes through pregnancy improves identification of women at increased risk of postpartum hemorrhage. This study provides greater understanding of the complex changes in blood count values that occur through pregnancy and provides indicators to guide the stratification of patients into risk groups.

Half and quarter metals in rhombohedral trilayer graphene - Zhou, Haoxin; Xie, Tian; Ghazaryan, Areg; Holder, Tobias; Ehrets, James R.; Spanton, Eric M.; Taniguchi, Takashi; Watanabe, Kenji; Berg, Erez; Serbyn, Maksym; Young, Andrea F. (Nature)
Ferromagnetism is most common in transition metal compounds but may also arise in low-density two-dimensional electron systems, with signatures observed in silicon, III-V semiconductor systems, and graphene moiré heterostructures. Here we show that gate-tuned van Hove singularities in rhombohedral trilayer graphene drive the spontaneous ferromagnetic polarization of the electron system into one or more spin- and valley flavors. Using capacitance measurements on graphite-gated van der Waals heterostructures, we find a cascade of density- and electronic displacement field tuned phase transitions marked by negative electronic compressibility. The transitions define the boundaries between phases where quantum oscillations have either four-fold, two-fold, or one-fold degeneracy, associated with a spin and valley degenerate normal metal, spin-polarized `half-metal', and spin and valley polarized `quarter metal', respectively. For electron doping, the salient features are well captured by a phenomenological Stoner model with a valley-anisotropic Hund's coupling, likely arising from interactions at the lattice scale. For hole filling, we observe a richer phase diagram featuring a delicate interplay of broken symmetries and transitions in the Fermi surface topology. Finally, by rotational alignment of a hexagonal boron nitride substrate to induce a moiré superlattice, we find that the superlattice perturbs the preexisting isospin order only weakly, leaving the basic phase diagram intact while catalyzing the formation of topologically nontrivial gapped states whenever itinerant half- or quarter metal states occur at half- or quarter superlattice band filling. Our results show that rhombohedral trilayer graphene is an ideal platform for well-controlled tests of many-body theory and reveal magnetism in moiré materials to be fundamentally itinerant in nature.
Keywords: condensed matter - mesoscale and nanoscale physics; condensed matter - strongly correlated electrons; multidisciplinary

Reactive key-loss protection in blockchains - Blackshear, Sam; Chalkias, Konstantinos; Chatzigiannis, Panagiotis; Faizullabhoy, Riyaz; Khaburzaniya, Irakliy; Kokoris Kogias, Eleftherios; Lind, Joshua; Wong, David; Zakian, Tim (FC 2021 Workshops)
We present a novel approach for blockchain asset owners to reclaim their funds in case of accidental private-key loss or transfer to a mistyped address. Our solution can be deployed upon failure or absence of proactively implemented backup mechanisms, such as secret sharing and cold storage. The main advantages against previous proposals is it does not require any prior action from users and works with both single-key and multi-sig accounts. We achieve this by a 3-phase Commit()→Reveal()→Claim()−or−Challenge() smart contract that enables accessing funds of addresses for which the spending key is not available. We provide an analysis of the threat and incentive models and formalize the concept of reactive KEy-Loss Protection (KELP).

Rademacher-type theorems and Sobolev-to-Lipschitz properties for strongly local Dirichlet spaces - Dello Schiavo, Lorenzo; Suzuki, Kohei (Journal of Functional Analysis)
We extensively discuss the Rademacher and Sobolev-to-Lipschitz properties for generalized intrinsic distances on strongly local Dirichlet spaces possibly without square field operator. We present many non-smooth and infinite-dimensional examples. As an application, we prove the integral Varadhan short-time asymptotic with respect to a given distance function for a large class of strongly local Dirichlet forms.

The importance of surface adsorbates in solution‐processed thermoelectric materials: The case of SnSe - Liu, Yu; Calcabrini, Mariano; Yu, Yuan; Genç, Aziz; Chang, Cheng; Costanzo, Tommaso; Kleinhanns, Tobias; Lee, Seungho; Llorca, Jordi; Cojocaru‐Mirédin, Oana; Ibáñez, Maria (Advanced Materials)
Solution synthesis of particles emerged as an alternative to prepare thermoelectric materials with less demanding processing conditions than conventional solid-state synthetic methods. However, solution synthesis generally involves the presence of additional molecules or ions belonging to the precursors or added to enable solubility and/or regulate nucleation and growth. These molecules or ions can end up in the particles as surface adsorbates and interfere in the material properties. This work demonstrates that ionic adsorbates, in particular Na⁺ ions, are electrostatically adsorbed in SnSe particles synthesized in water and play a crucial role not only in directing the material nano/microstructure but also in determining the transport properties of the consolidated material. In dense pellets prepared by sintering SnSe particles, Na remains within the crystal lattice as dopant, in dislocations, precipitates, and forming grain boundary complexions. These results highlight the importance of considering all the possible unintentional impurities to establish proper structure-property relationships and control material properties in solution-processed thermoelectric materials.
Keywords: mechanical engineering; mechanics of materials; general materials science

Interactome analysis of Caenorhabditis elegans synapses by TurboID-based proximity labeling - Artan, Murat; Barratt, Stephen; Flynn, Sean M.; Begum, Farida; Skehel, Mark; Nicolas, Armel; De Bono, Mario (Journal of Biological Chemistry)
Proximity labeling provides a powerful in vivo tool to characterize the proteome of subcellular structures and the interactome of specific proteins. The nematode Caenorhabditis elegans is one of the most intensely studied organisms in biology, offering many advantages for biochemistry. Using the highly active biotin ligase TurboID, we optimize here a proximity labeling protocol for C. elegans. An advantage of TurboID is that biotin's high affinity for streptavidin means biotin-labeled proteins can be affinity-purified under harsh denaturing conditions. By combining extensive sonication with aggressive denaturation using SDS and urea, we achieved near-complete solubilization of worm proteins. We then used this protocol to characterize the proteomes of the worm gut, muscle, skin, and nervous system. Neurons are among the smallest C. elegans cells. To probe the method's sensitivity, we expressed TurboID exclusively in the two AFD neurons and showed that the protocol could identify known and previously unknown proteins expressed selectively in AFD. The active zones of synapses are composed of a protein matrix that is difficult to solubilize and purify. To test if our protocol could solubilize active zone proteins, we knocked TurboID into the endogenous elks-1 gene, which encodes a presynaptic active zone protein. We identified many known ELKS-1-interacting active zone proteins, as well as previously uncharacterized synaptic proteins. Versatile vectors and the inherent advantages of using C. elegans, including fast growth and the ability to rapidly make and functionally test knock-ins, make proximity labeling a valuable addition to the armory of this model organism.

Differential monitoring - Mühlböck, Fabian; Henzinger, Thomas A (International Conference on Runtime Verification)
We argue that the time is ripe to investigate differential monitoring, in which the specification of a program's behavior is implicitly given by a second program implementing the same informal specification. Similar ideas have been proposed before, and are currently implemented in restricted form for testing and specialized run-time analyses, aspects of which we combine. We discuss the challenges of implementing differential monitoring as a general-purpose, black-box run-time monitoring framework, and present promising results of a preliminary implementation, showing low monitoring overheads for diverse programs.
Keywords: run-time verification; software engineering; implicit specification

Neuronal calmodulin levels are controlled by CAMTA transcription factors - Vuong-Brender, Thanh; Flynn, Sean; Vallis, Yvonne; De Bono, Mario (eLife)
The ubiquitous Ca2+ sensor calmodulin (CaM) binds and regulates many proteins, including ion channels, CaM kinases, and calcineurin, according to Ca2+-CaM levels. What regulates neuronal CaM levels, is, however, unclear. CaM-binding transcription activators (CAMTAs) are ancient proteins expressed broadly in nervous systems and whose loss confers pleiotropic behavioral defects in flies, mice, and humans. Using Caenorhabditis elegans and Drosophila, we show that CAMTAs control neuronal CaM levels. The behavioral and neuronal Ca2+ signaling defects in mutants lacking camt-1, the sole C. elegans CAMTA, can be rescued by supplementing neuronal CaM. CAMT-1 binds multiple sites in the CaM promoter and deleting these sites phenocopies camt-1. Our data suggest CAMTAs mediate a conserved and general mechanism that controls neuronal CaM levels, thereby regulating Ca2+ signaling, physiology, and behavior.

A structural perspective of the role of IP6 in immature and mature retroviral assembly - Obr, Martin; Schur, Florian KM; Dick, Robert A. (Viruses)
The small cellular molecule inositol hexakisphosphate (IP6) has been known for ~20 years to promote the in vitro assembly of HIV-1 into immature virus-like particles. However, the molecular details underlying this effect have been determined only recently, with the identification of the IP6 binding site in the immature Gag lattice. IP6 also promotes formation of the mature capsid protein (CA) lattice via a second IP6 binding site, and enhances core stability, creating a favorable environment for reverse transcription. IP6 also enhances assembly of other retroviruses, from both the Lentivirus and the Alpharetrovirus genera. These findings suggest that IP6 may have a conserved function throughout the family Retroviridae. Here, we discuss the different steps in the viral life cycle that are influenced by IP6, and describe in detail how IP6 interacts with the immature and mature lattices of different retroviruses.
Keywords: virology; infectious diseases

Entanglement transitions from restricted Boltzmann machines - Medina Ramos, Raimel A; Vasseur, Romain; Serbyn, Maksym (Physical Review B)
The search for novel entangled phases of matter has lead to the recent discovery of a new class of “entanglement transitions,” exemplified by random tensor networks and monitored quantum circuits. Most known examples can be understood as some classical ordering transitions in an underlying statistical mechanics model, where entanglement maps onto the free-energy cost of inserting a domain wall. In this paper we study the possibility of entanglement transitions driven by physics beyond such statistical mechanics mappings. Motivated by recent applications of neural-network-inspired variational Ansätze, we investigate under what conditions on the variational parameters these Ansätze can capture an entanglement transition. We study the entanglement scaling of short-range restricted Boltzmann machine (RBM) quantum states with random phases. For uncorrelated random phases, we analytically demonstrate the absence of an entanglement transition and reveal subtle finite-size effects in finite-size numerical simulations. Introducing phases with correlations decaying as 1/r^α in real space, we observe three regions with a different scaling of entanglement entropy depending on the exponent α. We study the nature of the transition between these regions, finding numerical evidence for critical behavior. Our work establishes the presence of long-range correlated phases in RBM-based wave functions as a required ingredient for entanglement transitions.

Differential monitoring - Mühlböck, Fabian; Henzinger, Thomas A
We argue that the time is ripe to investigate differential monitoring, in which the specification of a program's behavior is implicitly given by a second program implementing the same informal specification. Similar ideas have been proposed before, and are currently implemented in restricted form for testing and specialized run-time analyses, aspects of which we combine. We discuss the challenges of implementing differential monitoring as a general-purpose, black-box run-time monitoring framework, and present promising results of a preliminary implementation, showing low monitoring overheads for diverse programs.
Keywords: run-time verification; software engineering; implicit specification

Enhanced thermoelectric performance by surface engineering in SnTe-PbS nanocomposites - Chang, Cheng; Ibáñez, Maria (Materials)
Thermoelectric materials enable the direct conversion between heat and electricity. SnTe is a promising candidate due to its high charge transport performance. Here, we prepared SnTe nanocomposites by employing an aqueous method to synthetize SnTe nanoparticles (NP), followed by a unique surface treatment prior NP consolidation. This synthetic approach allowed optimizing the charge and phonon transport synergistically. The novelty of this strategy was the use of a soluble PbS molecular complex prepared using a thiol-amine solvent mixture that upon blending is adsorbed on the SnTe NP surface. Upon consolidation with spark plasma sintering, SnTe-PbS nanocomposite is formed. The presence of PbS complexes significantly compensates for the Sn vacancy and increases the average grain size of the nanocomposite, thus improving the carrier mobility. Moreover, lattice thermal conductivity is also reduced by the Pb and S-induced mass and strain fluctuation. As a result, an enhanced ZT of ca. 0.8 is reached at 873 K. Our finding provides a novel strategy to conduct rational surface treatment on NP-based thermoelectrics.

Schistosome W-Linked genes inform temporal dynamics of sex chromosome evolution and suggest candidate for sex determination - Elkrewi, Marwan N; Moldovan, Mikhail A.; Picard, Marion A L; Vicoso, Beatriz (Molecular Biology and Evolution)
Schistosomes, the human parasites responsible for snail fever, are female-heterogametic. Different parts of their ZW sex chromosomes have stopped recombining in distinct lineages, creating “evolutionary strata” of various ages. Although the Z-chromosome is well characterized at the genomic and molecular level, the W-chromosome has remained largely unstudied from an evolutionary perspective, as only a few W-linked genes have been detected outside of the model species Schistosoma mansoni. Here, we characterize the gene content and evolution of the W-chromosomes of S. mansoni and of the divergent species S. japonicum. We use a combined RNA/DNA k-mer based pipeline to assemble around 100 candidate W-specific transcripts in each of the species. About half of them map to known protein coding genes, the majority homologous to S. mansoni Z-linked genes. We perform an extended analysis of the evolutionary strata present in the two species (including characterizing a previously undetected young stratum in S. japonicum) to infer patterns of sequence and expression evolution of W-linked genes at different time points after recombination was lost. W-linked genes show evidence of degeneration, including high rates of protein evolution and reduced expression. Most are found in young lineage-specific strata, with only a few high expression ancestral W-genes remaining, consistent with the progressive erosion of nonrecombining regions. Among these, the splicing factor u2af2 stands out as a promising candidate for primary sex determination, opening new avenues for understanding the molecular basis of the reproductive biology of this group.
Keywords: sex chromosomes; evolutionary strata; W-linked gene; sex determining gene; schistosome parasites

PHF3 regulates neuronal gene expression through the Pol II CTD reader domain SPOC - Appel, Lisa-Marie; Franke, Vedran; Bruno, Melania; Grishkovskaya, Irina; Kasiliauskaite, Aiste; Kaufmann, Tanja; Schoeberl, Ursula E.; Puchinger, Martin G.; Kostrhon, Sebastian; Ebenwaldner, Carmen; Sebesta, Marek; Beltzung, Etienne; et al. (Nature Communications)
The C-terminal domain (CTD) of the largest subunit of RNA polymerase II (Pol II) is a regulatory hub for transcription and RNA processing. Here, we identify PHD-finger protein 3 (PHF3) as a regulator of transcription and mRNA stability that docks onto Pol II CTD through its SPOC domain. We characterize SPOC as a CTD reader domain that preferentially binds two phosphorylated Serine-2 marks in adjacent CTD repeats. PHF3 drives liquid-liquid phase separation of phosphorylated Pol II, colocalizes with Pol II clusters and tracks with Pol II across the length of genes. PHF3 knock-out or SPOC deletion in human cells results in increased Pol II stalling, reduced elongation rate and an increase in mRNA stability, with marked derepression of neuronal genes. Key neuronal genes are aberrantly expressed in Phf3 knock-out mouse embryonic stem cells, resulting in impaired neuronal differentiation. Our data suggest that PHF3 acts as a prominent effector of neuronal gene regulation by bridging transcription with mRNA decay.
Keywords: general physics and astronomy; general biochemistry; genetics and molecular biology; general chemistry

Neural acceleration of scattering-aware color 3D printing - Rittig, Tobias; Sumin, Denis; Babaei, Vahid; Didyk, Piotr; Voloboy, Alexey; Wilkie, Alexander; Bickel, Bernd; Myszkowski, Karol; Weyrich, Tim; Křivánek, Jaroslav (Computer Graphics Forum)
With the wider availability of full-color 3D printers, color-accurate 3D-print preparation has received increased attention. A key challenge lies in the inherent translucency of commonly used print materials that blurs out details of the color texture. Previous work tries to compensate for these scattering effects through strategic assignment of colored primary materials to printer voxels. To date, the highest-quality approach uses iterative optimization that relies on computationally expensive Monte Carlo light transport simulation to predict the surface appearance from subsurface scattering within a given print material distribution; that optimization, however, takes in the order of days on a single machine. In our work, we dramatically speed up the process by replacing the light transport simulation with a data-driven approach. Leveraging a deep neural network to predict the scattering within a highly heterogeneous medium, our method performs around two orders of magnitude faster than Monte Carlo rendering while yielding optimization results of similar quality level. The network is based on an established method from atmospheric cloud rendering, adapted to our domain and extended by a physically motivated weight sharing scheme that substantially reduces the network size. We analyze its performance in an end-to-end print preparation pipeline and compare quality and runtime to alternative approaches, and demonstrate its generalization to unseen geometry and material values. This for the first time enables full heterogenous material optimization for 3D-print preparation within time frames in the order of the actual printing time.

Focusing of in-plane hyperbolic polaritons in van der Waals crystals with tailored infrared nanoantennas - Martín-Sánchez, Javier; Duan, Jiahua; Taboada-Gutiérrez, Javier; Álvarez-Pérez, Gonzalo; Voronin, Kirill V.; Prieto Gonzalez, Ivan; Ma, Weiliang; Bao, Qiaoliang; Volkov, Valentyn S.; Hillenbrand, Rainer; Nikitin, Alexey Y.; Alonso-González, Pablo (Science Advances)
Phonon polaritons (PhPs)—light coupled to lattice vibrations—with in-plane hyperbolic dispersion exhibit ray-like propagation with large wave vectors and enhanced density of optical states along certain directions on a surface. As such, they have raised a surge of interest, promising unprecedented manipulation of infrared light at the nanoscale in a planar circuitry. Here, we demonstrate focusing of in-plane hyperbolic PhPs propagating along thin slabs of α-MoO3. To that end, we developed metallic nanoantennas of convex geometries for both efficient launching and focusing of the polaritons. The foci obtained exhibit enhanced near-field confinement and absorption compared to foci produced by in-plane isotropic PhPs. Foci sizes as small as λp/4.5 = λ0/50 were achieved (λp is the polariton wavelength and λ0 is the photon wavelength). Focusing of in-plane hyperbolic polaritons introduces a first and most basic building block developing planar polariton optics using in-plane anisotropic van der Waals materials.

Structure and assembly of the mammalian mitochondrial supercomplex CIII2CIV - Vercellino, Irene; Sazanov, Leonid A (Nature)
The enzymes of the mitochondrial electron transport chain are key players of cell metabolism. Despite being active when isolated, in vivo they associate into supercomplexes1, whose precise role is debated. Supercomplexes CIII2CIV1-2 (refs. 2,3), CICIII2 (ref. 4) and CICIII2CIV (respirasome)5,6,7,8,9,10 exist in mammals, but in contrast to CICIII2 and the respirasome, to date the only known eukaryotic structures of CIII2CIV1-2 come from Saccharomyces cerevisiae11,12 and plants13, which have different organization. Here we present the first, to our knowledge, structures of mammalian (mouse and ovine) CIII2CIV and its assembly intermediates, in different conformations. We describe the assembly of CIII2CIV from the CIII2 precursor to the final CIII2CIV conformation, driven by the insertion of the N terminus of the assembly factor SCAF1 (ref. 14) deep into CIII2, while its C terminus is integrated into CIV. Our structures (which include CICIII2 and the respirasome) also confirm that SCAF1 is exclusively required for the assembly of CIII2CIV and has no role in the assembly of the respirasome. We show that CIII2 is asymmetric due to the presence of only one copy of subunit 9, which straddles both monomers and prevents the attachment of a second copy of SCAF1 to CIII2, explaining the presence of one copy of CIV in CIII2CIV in mammals. Finally, we show that CIII2 and CIV gain catalytic advantage when assembled into the supercomplex and propose a role for CIII2CIV in fine tuning the efficiency of electron transfer in the electron transport chain.

Topological field theory on r-spin surfaces and the Arf-invariant - Runkel, Ingo; Szegedy, Lorant (Journal of Mathematical Physics)
We give a combinatorial model for r-spin surfaces with parameterized boundary based on Novak (“Lattice topological field theories in two dimensions,” Ph.D. thesis, Universität Hamburg, 2015). The r-spin structure is encoded in terms of ℤ𝑟-valued indices assigned to the edges of a polygonal decomposition. This combinatorial model is designed for our state-sum construction of two-dimensional topological field theories on r-spin surfaces. We show that an example of such a topological field theory computes the Arf-invariant of an r-spin surface as introduced by Randal-Williams [J. Topol. 7, 155 (2014)] and Geiges et al. [Osaka J. Math. 49, 449 (2012)]. This implies, in particular, that the r-spin Arf-invariant is constant on orbits of the mapping class group, providing an alternative proof of that fact.

Neurotransmitter signaling regulates distinct phases of multimodal human interneuron migration - Bajaj, Sunanjay; Bagley, Joshua A.; Sommer, Christoph M; Vertesy, Abel; Nagumo Wong, Sakurako; Krenn, Veronica; Lévi-Strauss, Julie; Knoblich, Juergen A. (EMBO Journal)
Inhibitory GABAergic interneurons migrate over long distances from their extracortical origin into the developing cortex. In humans, this process is uniquely slow and prolonged, and it is unclear whether guidance cues unique to humans govern the various phases of this complex developmental process. Here, we use fused cerebral organoids to identify key roles of neurotransmitter signaling pathways in guiding the migratory behavior of human cortical interneurons. We use scRNAseq to reveal expression of GABA, glutamate, glycine, and serotonin receptors along distinct maturation trajectories across interneuron migration. We develop an image analysis software package, TrackPal, to simultaneously assess 48 parameters for entire migration tracks of individual cells. By chemical screening, we show that different modes of interneuron migration depend on distinct neurotransmitter signaling pathways, linking transcriptional maturation of interneurons with their migratory behavior. Altogether, our study provides a comprehensive quantitative analysis of human interneuron migration and its functional modulation by neurotransmitter signaling.

Bright single photon emitters with enhanced quantum efficiency in a two-dimensional semiconductor coupled with dielectric nano-antennas - Sortino, Luca; Zotev, Panaiot G.; Phillips, Catherine L.; Brash, Alistair J.; Cambiasso, Javier; Marensi, Elena; Fox, A. Mark; Maier, Stefan A.; Sapienza, Riccardo; Tartakovskii, Alexander I. (Nature Communications)
Single photon emitters in atomically-thin semiconductors can be deterministically positioned using strain induced by underlying nano-structures. Here, we couple monolayer WSe2 to high-refractive-index gallium phosphide dielectric nano-antennas providing both optical enhancement and monolayer deformation. For single photon emitters formed on such nano-antennas, we find very low (femto-Joule) saturation pulse energies and up to 104 times brighter photoluminescence than in WSe2 placed on low-refractive-index SiO2 pillars. We show that the key to these observations is the increase on average by a factor of 5 of the quantum efficiency of the emitters coupled to the nano-antennas. This further allows us to gain new insights into their photoluminescence dynamics, revealing the roles of the dark exciton reservoir and Auger processes. We also find that the coherence time of such emitters is limited by intrinsic dephasing processes. Our work establishes dielectric nano-antennas as a platform for high-efficiency quantum light generation in monolayer semiconductors.

Geometric signatures of tissue surface tension in a three-dimensional model of confluent tissue - Sahu, Preeti; Schwarz, J. M.; Manning, M. Lisa (New Journal of Physics)
In dense biological tissues, cell types performing different roles remain segregated by maintaining sharp interfaces. To better understand the mechanisms for such sharp compartmentalization, we study the effect of an imposed heterotypic tension at the interface between two distinct cell types in a fully 3D Voronoi model for confluent tissues. We find that cells rapidly sort and self-organize to generate a tissue-scale interface between cell types, and cells adjacent to this interface exhibit signature geometric features including nematic-like ordering, bimodal facet areas, and registration, or alignment, of cell centers on either side of the two-tissue interface. The magnitude of these features scales directly with the magnitude of the imposed tension, suggesting that biologists can estimate the magnitude of tissue surface tension between two tissue types simply by segmenting a 3D tissue. To uncover the underlying physical mechanisms driving these geometric features, we develop two minimal, ordered models using two different underlying lattices that identify an energetic competition between bulk cell shapes and tissue interface area. When the interface area dominates, changes to neighbor topology are costly and occur less frequently, which generates the observed geometric features.

Rectifiable curves in proximally smooth sets - Ivanov, Grigory; Lopushanski, Mariana S. (Set-Valued and Variational Analysis)
In this article we study some geometric properties of proximally smooth sets. First, we introduce a modification of the metric projection and prove its existence. Then we provide an algorithm for constructing a rectifiable curve between two sufficiently close points of a proximally smooth set in a uniformly convex and uniformly smooth Banach space, with the moduli of smoothness and convexity of power type. Our algorithm returns a reasonably short curve between two sufficiently close points of a proximally smooth set, is iterative and uses our modification of the metric projection. We estimate the length of the constructed curve and its deviation from the segment with the same endpoints. These estimates coincide up to a constant factor with those for the geodesics in a proximally smooth set in a Hilbert space.

Satb2 acts as a gatekeeper for major developmental transitions during early vertebrate embryogenesis - Pradhan, Saurabh J.; Reddy, Puli Chandramouli; Smutny, Michael; Sharma, Ankita; Sako, Keisuke; Oak, Meghana S.; Shah, Rini; Pal, Mrinmoy; Deshpande, Ojas; Dsilva, Greg; Tang, Yin; Mishra, Rakesh; et al. (Nature Communications)
Zygotic genome activation (ZGA) initiates regionalized transcription underlying distinct cellular identities. ZGA is dependent upon dynamic chromatin architecture sculpted by conserved DNA-binding proteins. However, the direct mechanistic link between the onset of ZGA and the tissue-specific transcription remains unclear. Here, we have addressed the involvement of chromatin organizer Satb2 in orchestrating both processes during zebrafish embryogenesis. Integrative analysis of transcriptome, genome-wide occupancy and chromatin accessibility reveals contrasting molecular activities of maternally deposited and zygotically synthesized Satb2. Maternal Satb2 prevents premature transcription of zygotic genes by influencing the interplay between the pluripotency factors. By contrast, zygotic Satb2 activates transcription of the same group of genes during neural crest development and organogenesis. Thus, our comparative analysis of maternal versus zygotic function of Satb2 underscores how these antithetical activities are temporally coordinated and functionally implemented highlighting the evolutionary implications of the biphasic and bimodal regulation of landmark developmental transitions by a single determinant.

Uncovering Key Metabolic Determinants of the Drug Interactions Between Trimethoprim and Erythromycin in Escherichia coli - Qi, Qin; Angermayr, S. Andreas; Bollenbach, Mark Tobias (Frontiers in Microbiology)
Understanding interactions between antibiotics used in combination is an important theme in microbiology. Using the interactions between the antifolate drug trimethoprim and the ribosome-targeting antibiotic erythromycin in Escherichia coli as a model, we applied a transcriptomic approach for dissecting interactions between two antibiotics with different modes of action. When trimethoprim and erythromycin were combined, the transcriptional response of genes from the sulfate reduction pathway deviated from the dominant effect of trimethoprim on the transcriptome. We successfully altered the drug interaction from additivity to suppression by increasing the sulfate level in the growth environment and identified sulfate reduction as an important metabolic determinant that shapes the interaction between the two drugs. Our work highlights the potential of using prioritization of gene expression patterns as a tool for identifying key metabolic determinants that shape drug-drug interactions. We further demonstrated that the sigma factor-binding protein gene crl shapes the interactions between the two antibiotics, which provides a rare example of how naturally occurring variations between strains of the same bacterial species can sometimes generate very different drug interactions.
Keywords: microbiology

Eigenstate thermalization hypothesis for Wigner matrices - Cipolloni, Giorgio; Erdös, László; Schröder, Dominik J (Communications in Mathematical Physics)
We prove that any deterministic matrix is approximately the identity in the eigenbasis of a large random Wigner matrix with very high probability and with an optimal error inversely proportional to the square root of the dimension. Our theorem thus rigorously verifies the Eigenstate Thermalisation Hypothesis by Deutsch (Phys Rev A 43:2046–2049, 1991) for the simplest chaotic quantum system, the Wigner ensemble. In mathematical terms, we prove the strong form of Quantum Unique Ergodicity (QUE) with an optimal convergence rate for all eigenvectors simultaneously, generalizing previous probabilistic QUE results in Bourgade and Yau (Commun Math Phys 350:231–278, 2017) and Bourgade et al. (Commun Pure Appl Math 73:1526–1596, 2020).

The strongly coupled polaron on the torus: Quantum corrections to the Pekar asymptotics - Feliciangeli, Dario; Seiringer, Robert (Archive for Rational Mechanics and Analysis)
We investigate the Fröhlich polaron model on a three-dimensional torus, and give a proof of the second-order quantum corrections to its ground-state energy in the strong-coupling limit. Compared to previous work in the confined case, the translational symmetry (and its breaking in the Pekar approximation) makes the analysis substantially more challenging.

Translating the role of mtor-and ras-associated signalopathies in autism spectrum disorder: Models, mechanisms and treatment - Vasic, Verica; Jones, Mattson S.O.; Haslinger, Denise; Knaus, Lisa; Schmeisser, Michael J.; Novarino, Gaia; Chiocchetti, Andreas G. (Genes)
Mutations affecting mTOR or RAS signaling underlie defined syndromes (the so-called mTORopathies and RASopathies) with high risk for Autism Spectrum Disorder (ASD). These syndromes show a broad variety of somatic phenotypes including cancers, skin abnormalities, heart disease and facial dysmorphisms. Less well studied are the neuropsychiatric symptoms such as ASD. Here, we assess the relevance of these signalopathies in ASD reviewing genetic, human cell model, rodent studies and clinical trials. We conclude that signalopathies have an increased liability for ASD and that, in particular, ASD individuals with dysmorphic features and intellectual disability (ID) have a higher chance for disruptive mutations in RAS- and mTOR-related genes. Studies on rodent and human cell models confirm aberrant neuronal development as the underlying pathology. Human studies further suggest that multiple hits are necessary to induce the respective phenotypes. Recent clinical trials do only report improvements for comorbid conditions such as epilepsy or cancer but not for behavioral aspects. Animal models show that treatment during early development can rescue behavioral phenotypes. Taken together, we suggest investigating the differential roles of mTOR and RAS signaling in both human and rodent models, and to test drug treatment both during and after neuronal development in the available model systems

Mutually opposing activity of PIN7 splicing isoforms is required for auxin-mediated tropic responses in Arabidopsis thaliana - Kashkan, Ivan; Hrtyan, Mónika; Retzer, Katarzyna; Humpolíčková, Jana; Jayasree, Aswathy; Filepová, Roberta; Vondráková, Zuzana; Simon, Sibu; Rombaut, Debbie; Jacobs, Thomas B.; Frilander, Mikko J.; Hejátko, Jan; et al. (New Phytologist)
Advanced transcriptome sequencing has revealed that the majority of eukaryotic genes undergo alternative splicing (AS). Nonetheless, little effort has been dedicated to investigating the functional relevance of particular splicing events, even those in the key developmental and hormonal regulators. Combining approaches of genetics, biochemistry and advanced confocal microscopy, we describe the impact of alternative splicing on the PIN7 gene in the model plant Arabidopsis thaliana. PIN7 encodes a polarly localized transporter for the phytohormone auxin and produces two evolutionarily conserved transcripts, PIN7a and PIN7b. PIN7a and PIN7b, differing in a four amino acid stretch, exhibit almost identical expression patterns and subcellular localization. We reveal that they are closely associated and mutually influence each other's mobility within the plasma membrane. Phenotypic complementation tests indicate that the functional contribution of PIN7b per se is minor, but it markedly reduces the prominent PIN7a activity, which is required for correct seedling apical hook formation and auxin-mediated tropic responses. Our results establish alternative splicing of the PIN family as a conserved, functionally relevant mechanism, revealing an additional regulatory level of auxin-mediated plant development.

Eliminating higher-multiplicity intersections. III. Codimension 2 - Avvakumov, Sergey; Mabillard, Isaac; Skopenkov, Arkadiy B.; Wagner, Uli (Israel Journal of Mathematics)
We study conditions under which a finite simplicial complex K can be mapped to ℝd without higher-multiplicity intersections. An almost r-embedding is a map f: K → ℝd such that the images of any r pairwise disjoint simplices of K do not have a common point. We show that if r is not a prime power and d ≥ 2r + 1, then there is a counterexample to the topological Tverberg conjecture, i.e., there is an almost r-embedding of the (d +1)(r − 1)-simplex in ℝd. This improves on previous constructions of counterexamples (for d ≥ 3r) based on a series of papers by M. Özaydin, M. Gromov, P. Blagojević, F. Frick, G. Ziegler, and the second and fourth present authors. The counterexamples are obtained by proving the following algebraic criterion in codimension 2: If r ≥ 3 and if K is a finite 2(r − 1)-complex, then there exists an almost r-embedding K → ℝ2r if and only if there exists a general position PL map f: K → ℝ2r such that the algebraic intersection number of the f-images of any r pairwise disjoint simplices of K is zero. This result can be restated in terms of a cohomological obstruction and extends an analogous codimension 3 criterion by the second and fourth authors. As another application, we classify ornaments f: S3 ⊔ S3 ⊔ S3 → ℝ5 up to ornament concordance. It follows from work of M. Freedman, V. Krushkal and P. Teichner that the analogous criterion for r = 2 is false. We prove a lemma on singular higher-dimensional Borromean rings, yielding an elementary proof of the counterexample.

Early queen infection shapes developmental dynamics and induces long-term disease protection in incipient ant colonies - Casillas Perez, Barbara E; Pull, Christopher; Naiser, Filip; Naderlinger, Elisabeth; Matas, Jiri; Cremer, Sylvia
Infections early in life can have enduring effects on an organism’s development and immunity. In this study, we show that this equally applies to developing “superorganisms” – incipient social insect colonies. When we exposed newly mated Lasius niger ant queens to a low pathogen dose, their colonies grew more slowly than controls before winter, but reached similar sizes afterwards. Independent of exposure, queen hibernation survival improved when the ratio of pupae to workers was small. Queens that reared fewer pupae before worker emergence exhibited lower pathogen levels, indicating that high brood rearing efforts interfere with the ability of the queen’s immune system to suppress pathogen proliferation. Early-life queen pathogen-exposure also improved the immunocompetence of her worker offspring, as demonstrated by challenging the workers to the same pathogen a year later. Transgenerational transfer of the queen’s pathogen experience to her workforce can hence durably reduce the disease susceptibility of the whole superorganism.

Control of protein synthesis and memory by GluN3A-NMDA receptors through inhibition of GIT1/mTORC1 assembly - Conde-Dusman, María J; Dey, Partha N; Elía-Zudaire, Óscar; Garcia Rabaneda, Luis E; García-Lira, Carmen; Grand, Teddy; Briz, Victor; Velasco, Eric R; Andero Galí, Raül; Niñerola, Sergio; Barco, Angel; Paoletti, Pierre; et al. (eLife)
De novo protein synthesis is required for synapse modifications underlying stable memory encoding. Yet neurons are highly compartmentalized cells and how protein synthesis can be regulated at the synapse level is unknown. Here, we characterize neuronal signaling complexes formed by the postsynaptic scaffold GIT1, the mechanistic target of rapamycin (mTOR) kinase, and Raptor that couple synaptic stimuli to mTOR-dependent protein synthesis; and identify NMDA receptors containing GluN3A subunits as key negative regulators of GIT1 binding to mTOR. Disruption of GIT1/mTOR complexes by enhancing GluN3A expression or silencing GIT1 inhibits synaptic mTOR activation and restricts the mTOR-dependent translation of specific activity-regulated mRNAs. Conversely, GluN3A removal enables complex formation, potentiates mTOR-dependent protein synthesis, and facilitates the consolidation of associative and spatial memories in mice. The memory enhancement becomes evident with light or spaced training, can be achieved by selectively deleting GluN3A from excitatory neurons during adulthood, and does not compromise other aspects of cognition such as memory flexibility or extinction. Our findings provide mechanistic insight into synaptic translational control and reveal a potentially selective target for cognitive enhancement.
Keywords: general immunology and microbiology; general biochemistry; genetics and molecular biology; general medicine; general neuroscience

Towards best practices in research: Role of academic core facilities - Restivo, Leonardo; Gerlach, Björn; Tsoory, Michael; Bikovski, Lior; Badurek, Sylvia; Pitzer, Claudia; Kos-Braun, Isabelle C.; Mausset-Bonnefont, Anne Laure Mj; Ward, Jonathan; Schunn, Michael; Noldus, Lucas P.J.J.; Bespalov, Anton; et al. (EMBO Reports)
During the past decade, the scientific community and outside observers have noted a concerning lack of rigor and transparency in preclinical research that led to talk of a “reproducibility crisis” in the life sciences (Baker, 2016; Bespalov & Steckler, 2018; Heddleston et al, 2021). Various measures have been proposed to address the problem: from better training of scientists to more oversight to expanded publishing practices such as preregistration of studies. The recently published EQIPD (Enhancing Quality in Preclinical Data) System is, to date, the largest initiative that aims to establish a systematic approach for increasing the robustness and reliability of biomedical research (Bespalov et al, 2021). However, promoting a cultural change in research practices warrants a broad adoption of the Quality System and its underlying philosophy. It is here that academic Core Facilities (CF), research service providers at universities and research institutions, can make a difference. It is fair to assume that a significant fraction of published data originated from experiments that were designed, run, or analyzed in CFs. These academic services play an important role in the research ecosystem by offering access to cutting-edge equipment and by developing and testing novel techniques and methods that impact research in the academic and private sectors alike (Bikovski et al, 2020). Equipment and infrastructure are not the only value: CFs employ competent personnel with profound knowledge and practical experience of the specific field of interest: animal behavior, imaging, crystallography, genomics, and so on. Thus, CFs are optimally positioned to address concerns about the quality and robustness of preclinical research.

Cryo-EM structure of a functional monomeric Photosystem I from Thermosynechococcus elongatus reveals red chlorophyll cluster - Çoruh, Mehmet Orkun; Frank, Anna; Tanaka, Hideaki; Kawamoto, Akihiro; El-Mohsnawy, Eithar; Kato, Takayuki; Namba, Keiichi; Gerle, Christoph; Nowaczyk, Marc M.; Kurisu, Genji (Communications Biology)
A high-resolution structure of trimeric cyanobacterial Photosystem I (PSI) from Thermosynechococcus elongatus was reported as the first atomic model of PSI almost 20 years ago. However, the monomeric PSI structure has not yet been reported despite long-standing interest in its structure and extensive spectroscopic characterization of the loss of red chlorophylls upon monomerization. Here, we describe the structure of monomeric PSI from Thermosynechococcus elongatus BP-1. Comparison with the trimer structure gave detailed insights into monomerization-induced changes in both the central trimerization domain and the peripheral regions of the complex. Monomerization-induced loss of red chlorophylls is assigned to a cluster of chlorophylls adjacent to PsaX. Based on our findings, we propose a role of PsaX in the stabilization of red chlorophylls and that lipids of the surrounding membrane present a major source of thermal energy for uphill excitation energy transfer from red chlorophylls to P700.
Keywords: general agricultural and biological Sciences; general biochemistry; genetics and molecular biology; medicine (miscellaneous)

A coupled mechano-biochemical model for cell polarity guided anisotropic root growth - Marconi, Marco; Gallemi, Marçal; Benková, Eva; Wabnik, Krzysztof (eLife)
Plants develop new organs to adjust their bodies to dynamic changes in the environment. How independent organs achieve anisotropic shapes and polarities is poorly understood. To address this question, we constructed a mechano-biochemical model for Arabidopsis root meristem growth that integrates biologically plausible principles. Computer model simulations demonstrate how differential growth of neighboring tissues results in the initial symmetry-breaking leading to anisotropic root growth. Furthermore, the root growth feeds back on a polar transport network of the growth regulator auxin. Model, predictions are in close agreement with in vivo patterns of anisotropic growth, auxin distribution, and cell polarity, as well as several root phenotypes caused by chemical, mechanical, or genetic perturbations. Our study demonstrates that the combination of tissue mechanics and polar auxin transport organizes anisotropic root growth and cell polarities during organ outgrowth. Therefore, a mobile auxin signal transported through immobile cells drives polarity and growth mechanics to coordinate complex organ development.

Experimental observation of the origin and structure of elastoinertial turbulence - Choueiri, George H; Lopez Alonso, Jose M; Varshney, Atul; Sankar, Sarath; Hof, Björn (Proceedings of the National Academy of Sciences)
Turbulence generally arises in shear flows if velocities and hence, inertial forces are sufficiently large. In striking contrast, viscoelastic fluids can exhibit disordered motion even at vanishing inertia. Intermediate between these cases, a state of chaotic motion, “elastoinertial turbulence” (EIT), has been observed in a narrow Reynolds number interval. We here determine the origin of EIT in experiments and show that characteristic EIT structures can be detected across an unexpectedly wide range of parameters. Close to onset, a pattern of chevron-shaped streaks emerges in qualitative agreement with linear and weakly nonlinear theory. However, in experiments, the dynamics remain weakly chaotic, and the instability can be traced to far lower Reynolds numbers than permitted by theory. For increasing inertia, the flow undergoes a transformation to a wall mode composed of inclined near-wall streaks and shear layers. This mode persists to what is known as the “maximum drag reduction limit,” and overall EIT is found to dominate viscoelastic flows across more than three orders of magnitude in Reynolds number.
Keywords: multidisciplinary; elastoinertial turbulence; viscoelastic flows; elastic instability; drag reduction

Metamachines of pluripotent colloids - Aubret, Antoine; Martinet, Quentin; Palacci, Jérémie A (Nature Communications)
Machines enabled the Industrial Revolution and are central to modern technological progress: A machine’s parts transmit forces, motion, and energy to one another in a predetermined manner. Today’s engineering frontier, building artificial micromachines that emulate the biological machinery of living organisms, requires faithful assembly and energy consumption at the microscale. Here, we demonstrate the programmable assembly of active particles into autonomous metamachines using optical templates. Metamachines, or machines made of machines, are stable, mobile and autonomous architectures, whose dynamics stems from the geometry. We use the interplay between anisotropic force generation of the active colloids with the control of their orientation by local geometry. This allows autonomous reprogramming of active particles of the metamachines to achieve multiple functions. It permits the modular assembly of metamachines by fusion, reconfiguration of metamachines and, we anticipate, a shift in focus of self-assembly towards active matter and reprogrammable materials.

Neuronal HSF-1 coordinates the propagation of fat desaturation across tissues to enable adaptation to high temperatures in C. elegans - Chauve, Laetitia; Hodge, Francesca; Murdoch, Sharlene; Masoudzadeh, Fatemah; Mann, Harry Jack; Lopez-Clavijo, Andrea; Okkenhaug, Hanneke; West, Greg; Sousa, Bebiana C.; Segonds-Pichon, Anne; Li, Cheryl; Wingett, Steven; et al. (PLoS Biology)
To survive elevated temperatures, ectotherms adjust the fluidity of membranes by fine-tuning lipid desaturation levels in a process previously described to be cell autonomous. We have discovered that, in Caenorhabditis elegans, neuronal heat shock factor 1 (HSF-1), the conserved master regulator of the heat shock response (HSR), causes extensive fat remodeling in peripheral tissues. These changes include a decrease in fat desaturase and acid lipase expression in the intestine and a global shift in the saturation levels of plasma membrane’s phospholipids. The observed remodeling of plasma membrane is in line with ectothermic adaptive responses and gives worms a cumulative advantage to warm temperatures. We have determined that at least 6 TAX-2/TAX-4 cyclic guanosine monophosphate (cGMP) gated channel expressing sensory neurons, and transforming growth factor ß (TGF-β)/bone morphogenetic protein (BMP) are required for signaling across tissues to modulate fat desaturation. We also find neuronal hsf-1 is not only sufficient but also partially necessary to control the fat remodeling response and for survival at warm temperatures. This is the first study to show that a thermostat-based mechanism can cell nonautonomously coordinate membrane saturation and composition across tissues in a multicellular animal.

The beauty of random polytopes inscribed in the 2-sphere - Akopyan, Arseniy; Edelsbrunner, Herbert; Nikitenko, Anton (Experimental Mathematics)
Consider a random set of points on the unit sphere in ℝd, which can be either uniformly sampled or a Poisson point process. Its convex hull is a random inscribed polytope, whose boundary approximates the sphere. We focus on the case d = 3, for which there are elementary proofs and fascinating formulas for metric properties. In particular, we study the fraction of acute facets, the expected intrinsic volumes, the total edge length, and the distance to a fixed point. Finally we generalize the results to the ellipsoid with homeoid density.

How do chaperones bind (partly) unfolded client proteins? - Sučec, Iva; Bersch, Beate; Schanda, Paul (Frontiers in Molecular Biosciences)
Molecular chaperones are central to cellular protein homeostasis. Dynamic disorder is a key feature of the complexes of molecular chaperones and their client proteins, and it facilitates the client release towards a folded state or the handover to downstream components. The dynamic nature also implies that a given chaperone can interact with many different client proteins, based on physico-chemical sequence properties rather than on structural complementarity of their (folded) 3D structure. Yet, the balance between this promiscuity and some degree of client specificity is poorly understood. Here, we review recent atomic-level descriptions of chaperones with client proteins, including chaperones in complex with intrinsically disordered proteins, with membrane-protein precursors, or partially folded client proteins. We focus hereby on chaperone-client interactions that are independent of ATP. The picture emerging from these studies highlights the importance of dynamics in these complexes, whereby several interaction types, not only hydrophobic ones, contribute to the complex formation. We discuss these features of chaperone-client complexes and possible factors that may contribute to this balance of promiscuity and specificity.

Catabolism of strigolactones by a carboxylesterase - Xu, Enjun; Chai, Liang; Zhang, Shiqi; Yu, Ruixue; Zhang, Xixi; Xu, Chongyi; Hu, Yuxin (Nature Plants)
Strigolactones (SLs) are carotenoid-derived plant hormones that control shoot branching and communications between host plants and symbiotic fungi or root parasitic plants. Extensive studies have identified the key components participating in SL biosynthesis and signalling, whereas the catabolism or deactivation of endogenous SLs in planta remains largely unknown. Here, we report that the Arabidopsis carboxylesterase 15 (AtCXE15) and its orthologues function as efficient hydrolases of SLs. We show that overexpression of AtCXE15 promotes shoot branching by dampening SL-inhibited axillary bud outgrowth. We further demonstrate that AtCXE15 could bind and efficiently hydrolyse SLs both in vitro and in planta. We also provide evidence that AtCXE15 is capable of catalysing hydrolysis of diverse SL analogues and that such CXE15-dependent catabolism of SLs is evolutionarily conserved in seed plants. These results disclose a catalytic mechanism underlying homoeostatic regulation of SLs in plants, which also provides a rational approach to spatial-temporally manipulate the endogenous SLs and thus architecture of crops and ornamental plants.

Neuronal HSF-1 coordinates the propagation of fat desaturation across tissues to enable adaptation to high temperatures in C. elegans - Chauve, Laetitia; Hodge, Francesca; Murdoch, Sharlene; Masoudzadeh, Fatemah; Mann, Harry-Jack; Lopez-Clavijo, Andrea; Okkenhaug, Hanneke; West, Greg; Sousa, Bebiana C.; Segonds-Pichon, Anne; Li, Cheryl; Wingett, Steven; et al.
To survive elevated temperatures, ectotherms adjust the fluidity of membranes by fine-tuning lipid desaturation levels in a process previously described to be cell-autonomous. We have discovered that, in Caenorhabditis elegans, neuronal Heat shock Factor 1 (HSF-1), the conserved master regulator of the heat shock response (HSR)- causes extensive fat remodelling in peripheral tissues. These changes include a decrease in fat desaturase and acid lipase expression in the intestine, and a global shift in the saturation levels of plasma membrane’s phospholipids. The observed remodelling of plasma membrane is in line with ectothermic adaptive responses and gives worms a cumulative advantage to warm temperatures. We have determined that at least six TAX-2/TAX-4 cGMP gated channel expressing sensory neurons and TGF-β/BMP are required for signalling across tissues to modulate fat desaturation. We also find neuronal hsf-1 is not only sufficient but also partially necessary to control the fat remodelling response and for survival at warm temperatures. This is the first study to show that a thermostat-based mechanism can cell non-autonomously coordinate membrane saturation and composition across tissues in a multicellular animal.

SoK: Communication across distributed ledgers - Zamyatin, Alexei; Al-Bassam, Mustafa; Zindros, Dionysis; Kokoris Kogias, Eleftherios; Moreno-Sanchez, Pedro; Kiayias, Aggelos; Knottenbelt, William J. (25th International Conference on Financial Cryptography and Data Security)
Since the inception of Bitcoin, a plethora of distributed ledgers differing in design and purpose has been created. While by design, blockchains provide no means to securely communicate with external systems, numerous attempts towards trustless cross-chain communication have been proposed over the years. Today, cross-chain communication (CCC) plays a fundamental role in cryptocurrency exchanges, scalability efforts via sharding, extension of existing systems through sidechains, and bootstrapping of new blockchains. Unfortunately, existing proposals are designed ad-hoc for specific use-cases, making it hard to gain confidence in their correctness and composability. We provide the first systematic exposition of cross-chain communication protocols. We formalize the underlying research problem and show that CCC is impossible without a trusted third party, contrary to common beliefs in the blockchain community. With this result in mind, we develop a framework to design new and evaluate existing CCC protocols, focusing on the inherent trust assumptions thereof, and derive a classification covering the field of cross-chain communication to date. We conclude by discussing open challenges for CCC research and the implications of interoperability on the security and privacy of blockchains.

Brick: Asynchronous incentive-compatible payment channels - Avarikioti, Zeta; Kokoris Kogias, Eleftherios; Wattenhofer, Roger; Zindros, Dionysis (25th International Conference on Financial Cryptography and Data Security)
Off-chain protocols (channels) are a promising solution to the scalability and privacy challenges of blockchain payments. Current proposals, however, require synchrony assumptions to preserve the safety of a channel, leaking to an adversary the exact amount of time needed to control the network for a successful attack. In this paper, we introduce Brick, the first payment channel that remains secure under network asynchrony and concurrently provides correct incentives. The core idea is to incorporate the conflict resolution process within the channel by introducing a rational committee of external parties, called wardens. Hence, if a party wants to close a channel unilaterally, it can only get the committee’s approval for the last valid state. Additionally, Brick provides sub-second latency because it does not employ heavy-weight consensus. Instead, Brick uses consistent broadcast to announce updates and close the channel, a light-weight abstraction that is powerful enough to preserve safety and liveness to any rational parties. We formally define and prove for Brick the properties a payment channel construction should fulfill. We also design incentives for Brick such that honest and rational behavior aligns. Finally, we provide a reference implementation of the smart contracts in Solidity.

Rational engineering of an erythropoietin fusion protein to treat hypoxia - Lee, Jungmin; Vernet, Andyna; Gruber, Nathalie; Kready, Kasia M.; Burrill, Devin R.; Way, Jeffrey C.; Silver, Pamela A. (Protein Engineering, Design and Selection)
Erythropoietin enhances oxygen delivery and reduces hypoxia-induced cell death, but its pro-thrombotic activity is problematic for use of erythropoietin in treating hypoxia. We constructed a fusion protein that stimulates red blood cell production and neuroprotection without triggering platelet production, a marker for thrombosis. The protein consists of an anti-glycophorin A nanobody and an erythropoietin mutant (L108A). The mutation reduces activation of erythropoietin receptor homodimers that induce erythropoiesis and thrombosis, but maintains the tissue-protective signaling. The binding of the nanobody element to glycophorin A rescues homodimeric erythropoietin receptor activation on red blood cell precursors. In a cell proliferation assay, the fusion protein is active at 10−14 M, allowing an estimate of the number of receptor–ligand complexes needed for signaling. This fusion protein stimulates erythroid cell proliferation in vitro and in mice, and shows neuroprotective activity in vitro. Our erythropoietin fusion protein presents a novel molecule for treating hypoxia.

Special rebranding issue: “Quantitative cell and developmental biology” - Heisenberg, Carl-Philipp J; Lennon, Ana Maria; Mayor, Roberto; Salbreux, Guillaume (Cells and Development)

Theory of branching morphogenesis by local interactions and global guidance - Ucar, Mehmet C; Kamenev, Dmitrii; Sunadome, Kazunori; Fachet, Dominik C; Lallemend, Francois; Adameyko, Igor; Hadjab, Saida; Hannezo, Edouard B (Nature Communications)
Branching morphogenesis governs the formation of many organs such as lung, kidney, and the neurovascular system. Many studies have explored system-specific molecular and cellular regulatory mechanisms, as well as self-organizing rules underlying branching morphogenesis. However, in addition to local cues, branched tissue growth can also be influenced by global guidance. Here, we develop a theoretical framework for a stochastic self-organized branching process in the presence of external cues. Combining analytical theory with numerical simulations, we predict differential signatures of global vs. local regulatory mechanisms on the branching pattern, such as angle distributions, domain size, and space-filling efficiency. We find that branch alignment follows a generic scaling law determined by the strength of global guidance, while local interactions influence the tissue density but not its overall territory. Finally, using zebrafish innervation as a model system, we test these key features of the model experimentally. Our work thus provides quantitative predictions to disentangle the role of different types of cues in shaping branched structures across scales.

Trojan-resilience without cryptography - Chakraborty, Suvradip; Dziembowski, Stefan; Gałązka, Małgorzata; Lizurej, Tomasz; Pietrzak, Krzysztof Z; Yeo, Michelle X
Digital hardware Trojans are integrated circuits whose implementation differ from the specification in an arbitrary and malicious way. For example, the circuit can differ from its specified input/output behavior after some fixed number of queries (known as “time bombs”) or on some particular input (known as “cheat codes”). To detect such Trojans, countermeasures using multiparty computation (MPC) or verifiable computation (VC) have been proposed. On a high level, to realize a circuit with specification F one has more sophisticated circuits F⋄ manufactured (where F⋄ specifies a MPC or VC of F ), and then embeds these F⋄ ’s into a master circuit which must be trusted but is relatively simple compared to F . Those solutions impose a significant overhead as F⋄ is much more complex than F , also the master circuits are not exactly trivial. In this work, we show that in restricted settings, where F has no evolving state and is queried on independent inputs, we can achieve a relaxed security notion using very simple constructions. In particular, we do not change the specification of the circuit at all (i.e., F=F⋄ ). Moreover the master circuit basically just queries a subset of its manufactured circuits and checks if they’re all the same. The security we achieve guarantees that, if the manufactured circuits are initially tested on up to T inputs, the master circuit will catch Trojans that try to deviate on significantly more than a 1/T fraction of the inputs. This bound is optimal for the type of construction considered, and we provably achieve it using a construction where 12 instantiations of F need to be embedded into the master. We also discuss an extremely simple construction with just 2 instantiations for which we conjecture that it already achieves the optimal bound.

Developmental emergence of two-stage nonlinear synaptic integration in cerebellar interneurons - Biane, Celia; Rückerl, Florian; Abrahamsson, Therese; Saint-Cloment, Cécile; Mariani, Jean; Shigemoto, Ryuichi; Digregorio, David A.; Sherrard, Rachel M.; Cathala, Laurence (eLife)
Synaptic transmission, connectivity, and dendritic morphology mature in parallel during brain development and are often disrupted in neurodevelopmental disorders. Yet how these changes influence the neuronal computations necessary for normal brain function are not well understood. To identify cellular mechanisms underlying the maturation of synaptic integration in interneurons, we combined patch-clamp recordings of excitatory inputs in mouse cerebellar stellate cells (SCs), three-dimensional reconstruction of SC morphology with excitatory synapse location, and biophysical modeling. We found that postnatal maturation of postsynaptic strength was homogeneously reduced along the somatodendritic axis, but dendritic integration was always sublinear. However, dendritic branching increased without changes in synapse density, leading to a substantial gain in distal inputs. Thus, changes in synapse distribution, rather than dendrite cable properties, are the dominant mechanism underlying the maturation of neuronal computation. These mechanisms favor the emergence of a spatially compartmentalized two-stage integration model promoting location-dependent integration within dendritic subunits.

Generation of spin currents by a temperature gradient in a two-terminal device - Barfknecht, Rafael E.; Foerster, Angela; Zinner, Nikolaj T.; Volosniev, Artem (Communications Physics)
Theoretical and experimental studies of the interaction between spins and temperature are vital for the development of spin caloritronics, as they dictate the design of future devices. In this work, we propose a two-terminal cold-atom simulator to study that interaction. The proposed quantum simulator consists of strongly interacting atoms that occupy two temperature reservoirs connected by a one-dimensional link. First, we argue that the dynamics in the link can be described using an inhomogeneous Heisenberg spin chain whose couplings are defined by the local temperature. Second, we show the existence of a spin current in a system with a temperature difference by studying the dynamics that follows the spin-flip of an atom in the link. A temperature gradient accelerates the impurity in one direction more than in the other, leading to an overall spin current similar to the spin Seebeck effect.

Interactive analysis of CNN robustness - Sietzen, Stefan; Lechner, Mathias; Borowski, Judy; Hasani, Ramin; Waldner, Manuela (Computer Graphics Forum)
While convolutional neural networks (CNNs) have found wide adoption as state-of-the-art models for image-related tasks, their predictions are often highly sensitive to small input perturbations, which the human vision is robust against. This paper presents Perturber, a web-based application that allows users to instantaneously explore how CNN activations and predictions evolve when a 3D input scene is interactively perturbed. Perturber offers a large variety of scene modifications, such as camera controls, lighting and shading effects, background modifications, object morphing, as well as adversarial attacks, to facilitate the discovery of potential vulnerabilities. Fine-tuned model versions can be directly compared for qualitative evaluation of their robustness. Case studies with machine learning experts have shown that Perturber helps users to quickly generate hypotheses about model vulnerabilities and to qualitatively compare model behavior. Using quantitative analyses, we could replicate users’ insights with other CNN architectures and input images, yielding new insights about the vulnerability of adversarially trained models.

Dissecting organismal morphogenesis by bridging genetics and biophysics - Mishra, Nikhil; Heisenberg, Carl-Philipp J (Annual Review of Genetics)
Multicellular organisms develop complex shapes from much simpler, single-celled zygotes through a process commonly called morphogenesis. Morphogenesis involves an interplay between several factors, ranging from the gene regulatory networks determining cell fate and differentiation to the mechanical processes underlying cell and tissue shape changes. Thus, the study of morphogenesis has historically been based on multidisciplinary approaches at the interface of biology with physics and mathematics. Recent technological advances have further improved our ability to study morphogenesis by bridging the gap between the genetic and biophysical factors through the development of new tools for visualizing, analyzing, and perturbing these factors and their biochemical intermediaries. Here, we review how a combination of genetic, microscopic, biophysical, and biochemical approaches has aided our attempts to understand morphogenesis and discuss potential approaches that may be beneficial to such an inquiry in the future.
Keywords: morphogenesis; forward genetics; high-resolution microscopy; biophysics; biochemistry; patterning

Source data for the manuscript "Theory of branching morphogenesis by local interactions and global guidance" - Ucar, Mehmet C
The zip file includes source data used in the main text of the manuscript "Theory of branching morphogenesis by local interactions and global guidance", as well as a representative Jupyter notebook to reproduce the main figures. A sample script for the simulations of branching and annihilating random walks is also included (Sample_script_for_simulations_of_BARWs.ipynb) to generate exemplary branched networks under external guidance. A detailed description of the simulation setup is provided in the supplementary information of the manuscipt.

Grafting key trees: Efficient key management for overlapping groups - Alwen, Joel F; Auerbach, Benedikt; Baig, Mirza Ahad; Cueto Noval, Miguel; Klein, Karen; Pascual Perez, Guillermo; Pietrzak, Krzysztof Z; Walter, Michael (19th International Conference)
Key trees are often the best solution in terms of transmission cost and storage requirements for managing keys in a setting where a group needs to share a secret key, while being able to efficiently rotate the key material of users (in order to recover from a potential compromise, or to add or remove users). Applications include multicast encryption protocols like LKH (Logical Key Hierarchies) or group messaging like the current IETF proposal TreeKEM. A key tree is a (typically balanced) binary tree, where each node is identified with a key: leaf nodes hold users’ secret keys while the root is the shared group key. For a group of size N, each user just holds log(N) keys (the keys on the path from its leaf to the root) and its entire key material can be rotated by broadcasting 2log(N) ciphertexts (encrypting each fresh key on the path under the keys of its parents). In this work we consider the natural setting where we have many groups with partially overlapping sets of users, and ask if we can find solutions where the cost of rotating a key is better than in the trivial one where we have a separate key tree for each group. We show that in an asymptotic setting (where the number m of groups is fixed while the number N of users grows) there exist more general key graphs whose cost converges to the cost of a single group, thus saving a factor linear in the number of groups over the trivial solution. As our asymptotic “solution” converges very slowly and performs poorly on concrete examples, we propose an algorithm that uses a natural heuristic to compute a key graph for any given group structure. Our algorithm combines two greedy algorithms, and is thus very efficient: it first converts the group structure into a “lattice graph”, which is then turned into a key graph by repeatedly applying the algorithm for constructing a Huffman code. To better understand how far our proposal is from an optimal solution, we prove lower bounds on the update cost of continuous group-key agreement and multicast encryption in a symbolic model admitting (asymmetric) encryption, pseudorandom generators, and secret sharing as building blocks.

Unconventional superconductivity in systems with annular Fermi surfaces: Application to rhombohedral trilayer graphene - Ghazaryan, Areg; Holder, Tobias; Serbyn, Maksym; Berg, Erez (Physical Review Letters)
We show that in a two-dimensional electron gas with an annular Fermi surface, long-range Coulomb interactions can lead to unconventional superconductivity by the Kohn-Luttinger mechanism. Superconductivity is strongly enhanced when the inner and outer Fermi surfaces are close to each other. The most prevalent state has chiral p-wave symmetry, but d-wave and extended s-wave pairing are also possible. We discuss these results in the context of rhombohedral trilayer graphene, where superconductivity was recently discovered in regimes where the normal state has an annular Fermi surface. Using realistic parameters, our mechanism can account for the order of magnitude of Tc, as well as its trends as a function of electron density and perpendicular displacement field. Moreover, it naturally explains some of the outstanding puzzles in this material, that include the weak temperature dependence of the resistivity above Tc, and the proximity of spin singlet superconductivity to the ferromagnetic phase.
Keywords: general physics and astronomy

Fullerene derivatives with oligoethylene-glycol side chains: An investigation on the origin of their outstanding transport properties - Dong, Jingjin; Sami, Selim; Balazs, Daniel; Alessandri, Riccardo; Jahani, Fatimeh; Qiu, Li; Marrink, Siewert J.; Havenith, Remco W.A.; Hummelen, Jan C.; Loi, Maria A.; Portale, Giuseppe (Journal of Materials Chemistry C)
For many years, fullerene derivatives have been the main n-type material of organic electronics and optoelectronics. Recently, fullerene derivatives functionalized with ethylene glycol (EG) side chains have been showing important properties such as enhanced dielectric constants, facile doping and enhanced self-assembly capabilities. Here, we have prepared field-effect transistors using a series of these fullerene derivatives equipped with EG side chains of different lengths. Transport data show the beneficial effect of increasing the EG side chain. In order to understand the material properties, full structural determination of these fullerene derivatives has been achieved by coupling the X-ray data with molecular dynamics (MD) simulations. The increase in transport properties is paired with the formation of extended layered structures, efficient molecular packing and an increase in the crystallite alignment. The layer-like structure is composed of conducting layers, containing of closely packed C60 balls approaching the inter-distance of 1 nm, that are separated by well-defined EG layers, where the EG chains are rather splayed with the chain direction almost perpendicular to the layer normal. Such a layered structure appears highly ordered and highly aligned with the C60 planes oriented parallel to the substrate in the thin film configuration. The order inside the thin film increases with the EG chain length, allowing the systems to achieve mobilities as high as 0.053 cm2 V−1 s−1. Our work elucidates the structure of these interesting semiconducting organic molecules and shows that the synergistic use of X-ray structural analysis and MD simulations is a powerful tool to identify the structure of thin organic films for optoelectronic applications.

Histone H1 prevents non-CG methylation-mediated small RNA biogenesis in Arabidopsis heterochromatin - Choi, Jaemyung; Lyons, David B; Zilberman, Daniel (eLife)
Flowering plants utilize small RNA molecules to guide DNA methyltransferases to genomic sequences. This RNA-directed DNA methylation (RdDM) pathway preferentially targets euchromatic transposable elements. However, RdDM is thought to be recruited by methylation of histone H3 at lysine 9 (H3K9me), a hallmark of heterochromatin. How RdDM is targeted to euchromatin despite an affinity for H3K9me is unclear. Here we show that loss of histone H1 enhances heterochromatic RdDM, preferentially at nucleosome linker DNA. Surprisingly, this does not require SHH1, the RdDM component that binds H3K9me. Furthermore, H3K9me is dispensable for RdDM, as is CG DNA methylation. Instead, we find that non-CG methylation is specifically associated with small RNA biogenesis, and without H1 small RNA production quantitatively expands to non-CG methylated loci. Our results demonstrate that H1 enforces the separation of euchromatic and heterochromatic DNA methylation pathways by excluding the small RNA-generating branch of RdDM from non-CG methylated heterochromatin.
Keywords: genetics and molecular biology

TGFβ signaling in myeloid cells promotes lung and liver metastasis through different mechanisms - Stefanescu, Cristina; Van Gogh, Merel; Roblek, Marko; Heikenwalder, Mathias; Borsig, Lubor (Frontiers in Oncology)
TGFβ overexpression is commonly detected in cancer patients and correlates with poor prognosis and metastasis. Cancer progression is often associated with an enhanced recruitment of myeloid-derived cells to the tumor microenvironment. Here we show that functional TGFβ-signaling in myeloid cells is required for metastasis to the lungs and the liver. Myeloid-specific deletion of Tgfbr2 resulted in reduced spontaneous lung metastasis, which was associated with a reduction of proinflammatory cytokines in the metastatic microenvironment. Notably, CD8+ T cell depletion in myeloid-specific Tgfbr2-deficient mice rescued lung metastasis. Myeloid-specific Tgfbr2-deficiency resulted in reduced liver metastasis with an almost complete absence of myeloid cells within metastatic foci. On contrary, an accumulation of Tgfβ-responsive myeloid cells was associated with an increased recruitment of monocytes and granulocytes and higher proinflammatory cytokine levels in control mice. Monocytic cells isolated from metastatic livers of Tgfbr2-deficient mice showed increased polarization towards the M1 phenotype, Tnfα and Il-1β expression, reduced levels of M2 markers and reduced production of chemokines responsible for myeloid-cell recruitment. No significant differences in Tgfβ levels were observed at metastatic sites of any model. These data demonstrate that Tgfβ signaling in monocytic myeloid cells suppresses CD8+ T cell activity during lung metastasis, while these cells actively contribute to tumor growth during liver metastasis. Thus, myeloid cells modulate metastasis through different mechanisms in a tissue-specific manner.

Bosonization of fermionic many-body dynamics - Benedikter, Niels P; Nam, Phan Thành; Porta, Marcello; Schlein, Benjamin; Seiringer, Robert (Annales Henri Poincaré)
We consider the quantum many-body evolution of a homogeneous Fermi gas in three dimensions in the coupled semiclassical and mean-field scaling regime. We study a class of initial data describing collective particle–hole pair excitations on the Fermi ball. Using a rigorous version of approximate bosonization, we prove that the many-body evolution can be approximated in Fock space norm by a quasi-free bosonic evolution of the collective particle–hole excitations.

Optimal homogenization rates in stochastic homogenization of nonlinear uniformly elliptic equations and systems - Fischer, Julian L; Neukamm, Stefan (Archive for Rational Mechanics and Analysis)
We derive optimal-order homogenization rates for random nonlinear elliptic PDEs with monotone nonlinearity in the uniformly elliptic case. More precisely, for a random monotone operator on \mathbb {R}^d with stationary law (that is spatially homogeneous statistics) and fast decay of correlations on scales larger than the microscale \varepsilon >0, we establish homogenization error estimates of the order \varepsilon in case d\geqq 3, and of the order \varepsilon |\log \varepsilon |^{1/2} in case d=2. Previous results in nonlinear stochastic homogenization have been limited to a small algebraic rate of convergence \varepsilon ^\delta . We also establish error estimates for the approximation of the homogenized operator by the method of representative volumes of the order (L/\varepsilon )^{-d/2} for a representative volume of size L. Our results also hold in the case of systems for which a (small-scale) C^{1,\alpha } regularity theory is available.
Keywords: Mechanical Engineering; Mathematics (miscellaneous); Analysis

On treewidth, separators and Yao’s garbling - Kamath Hosdurg, Chethan; Klein, Karen; Pietrzak, Krzysztof Z (19th International Conference)
We show that Yao’s garbling scheme is adaptively indistinguishable for the class of Boolean circuits of size S and treewidth w with only a SO(w) loss in security. For instance, circuits with constant treewidth are as a result adaptively indistinguishable with only a polynomial loss. This (partially) complements a negative result of Applebaum et al. (Crypto 2013), which showed (assuming one-way functions) that Yao’s garbling scheme cannot be adaptively simulatable. As main technical contributions, we introduce a new pebble game that abstracts out our security reduction and then present a pebbling strategy for this game where the number of pebbles used is roughly O(δwlog(S)) , δ being the fan-out of the circuit. The design of the strategy relies on separators, a graph-theoretic notion with connections to circuit complexity. with only a SO(w) loss in security. For instance, circuits with constant treewidth are as a result adaptively indistinguishable with only a polynomial loss. This (partially) complements a negative result of Applebaum et al. (Crypto 2013), which showed (assuming one-way functions) that Yao’s garbling scheme cannot be adaptively simulatable. As main technical contributions, we introduce a new pebble game that abstracts out our security reduction and then present a pebbling strategy for this game where the number of pebbles used is roughly O(δwlog(S)) , δ being the fan-out of the circuit. The design of the strategy relies on separators, a graph-theoretic notion with connections to circuit complexity.

Duality approach to quantum annealing of the 3-variable exclusive-or satisfiability problem (3-XORSAT) - Medina Ramos, Raimel A; Serbyn, Maksym (Physical Review A)
Classical models with complex energy landscapes represent a perspective avenue for the near-term application of quantum simulators. Until now, many theoretical works studied the performance of quantum algorithms for models with a unique ground state. However, when the classical problem is in a so-called clustering phase, the ground state manifold is highly degenerate. As an example, we consider a 3-XORSAT model defined on simple hypergraphs. The degeneracy of classical ground state manifold translates into the emergence of an extensive number of Z2 symmetries, which remain intact even in the presence of a quantum transverse magnetic field. We establish a general duality approach that restricts the quantum problem to a given sector of conserved Z2 charges and use it to study how the outcome of the quantum adiabatic algorithm depends on the hypergraph geometry. We show that the tree hypergraph which corresponds to a classically solvable instance of the 3-XORSAT problem features a constant gap, whereas the closed hypergraph encounters a second-order phase transition with a gap vanishing as a power-law in the problem size. The duality developed in this work provides a practical tool for studies of quantum models with classically degenerate energy manifold and reveals potential connections between glasses and gauge theories.

All You Need is DAG - Keidar, Idit; Kokoris Kogias, Eleftherios; Naor, Oded; Spiegelman, Alexander (Proceedings of the 2021 ACM Symposium on Principles of Distributed Computing)
We present DAG-Rider, the first asynchronous Byzantine Atomic Broadcast protocol that achieves optimal resilience, optimal amortized communication complexity, and optimal time complexity. DAG-Rider is post-quantum safe and ensures that all values proposed by correct processes eventually get delivered. We construct DAG-Rider in two layers: In the first layer, processes reliably broadcast their proposals and build a structured Directed Acyclic Graph (DAG) of the communication among them. In the second layer, processes locally observe their DAGs and totally order all proposals with no extra communication.

Pipefish locally adapted to low salinity in the Baltic Sea retain phenotypic plasticity to cope with ancestral salinity levels - Goehlich, Henry; Sartoris, Linda; Wagner, Kim-Sara; Wendling, Carolin C.; Roth, Olivia (Frontiers in Ecology and Evolution)
Genetic adaptation and phenotypic plasticity facilitate the migration into new habitats and enable organisms to cope with a rapidly changing environment. In contrast to genetic adaptation that spans multiple generations as an evolutionary process, phenotypic plasticity allows acclimation within the life-time of an organism. Genetic adaptation and phenotypic plasticity are usually studied in isolation, however, only by including their interactive impact, we can understand acclimation and adaptation in nature. We aimed to explore the contribution of adaptation and plasticity in coping with an abiotic (salinity) and a biotic (Vibrio bacteria) stressor using six different populations of the broad-nosed pipefish Syngnathus typhle that originated from either high [14–17 Practical Salinity Unit (PSU)] or low (7–11 PSU) saline environments along the German coastline of the Baltic Sea. We exposed wild caught animals, to either high (15 PSU) or low (7 PSU) salinity, representing native and novel salinity conditions and allowed animals to mate. After male pregnancy, offspring was split and each half was exposed to one of the two salinities and infected with Vibrio alginolyticus bacteria that were evolved at either of the two salinities in a fully reciprocal design. We investigated life-history traits of fathers and expression of 47 target genes in mothers and offspring. Pregnant males originating from high salinity exposed to low salinity were highly susceptible to opportunistic fungi infections resulting in decreased offspring size and number. In contrast, no signs of fungal infection were identified in fathers originating from low saline conditions suggesting that genetic adaptation has the potential to overcome the challenges encountered at low salinity. Offspring from parents with low saline origin survived better at low salinity suggesting genetic adaptation to low salinity. In addition, gene expression analyses of juveniles indicated patterns of local adaptation, trans-generational plasticity and developmental plasticity. In conclusion, our study suggests that pipefish are locally adapted to the low salinity in their environment, however, they are retaining phenotypic plasticity, which allows them to also cope with ancestral salinity levels and prevailing pathogens.
Keywords: ecology; evolution; behavior and systematics; trans-generational plasticity; genetic adaptation; local adaptation; phenotypic plasticity; Baltic Sea; climate change; salinity; syngnathids

Fe2O3 nanoparticles deposited over self-floating facial sponge for facile interfacial seawater solar desalination - Lu, Yuzheng; Arshad, Naila; Irshad, Muhammad Sultan; Ahmed, Iftikhar; Ahmad, Shafiq; Alshahrani, Lina Abdullah; Yousaf, Muhammad; Sayed, Abdelaty Edrees; Nauman, Muhammad (Crystals)
A facile approach for developing an interfacial solar evaporator by heat localization of solar-thermal energy conversion at water-air liquid composed by in-situ polymerization of Fe2O3 nanoparticles (Fe2O3@PPy) deposited over a facial sponge is proposed. The demonstrated system consists of a floating solar receiver having a vertically cross-linked microchannel for wicking up saline water. The in situ polymerized Fe2O3@PPy interfacial layer promotes diffuse reflection and its rough black surface allows Omni-directional solar absorption (94%) and facilitates efficient thermal localization at the water/air interface and offers a defect-rich surface to promote heat localization (41.9 °C) and excellent thermal management due to cellulosic content. The self-floating composite foam reveals continuous vapors generation at a rate of 1.52 kg m−2 h−1 under one 1 kW m−2 and profound evaporating efficiency (95%) without heat losses that dissipates in its surroundings. Indeed, long-term evaporation experiments reveal the negligible disparity in continuous evaporation rate (33.84 kg m−2/8.3 h) receiving two sun solar intensity, and ensures the stability of the device under intense seawater conditions synchronized with excellent salt rejection potential. More importantly, Raman spectroscopy investigation validates the orange dye rejection via Fe2O3@PPy solar evaporator. The combined advantages of high efficiency, self-floating capability, multimedia rejection, low cost, and this configuration are promising for producing large-scale solar steam generating systems appropriate for commercial clean water yield due to their scalable fabrication.

Naïve poison frog tadpoles use bi-modal cues to avoid insect predators but not heterospecific predatory tadpoles - Szabo, B; Mangione, R; Rath, M; Pašukonis, A; Reber, SA; Oh, Jinook; Ringler, M; Ringler, E (Journal of Experimental Biology)
For animals to survive until reproduction, it is crucial that juveniles successfully detect potential predators and respond with appropriate behavior. The recognition of cues originating from predators can be innate or learned. Cues of various modalities might be used alone or in multi-modal combinations to detect and distinguish predators but studies investigating multi-modal integration in predator avoidance are scarce. Here, we used wild, naive tadpoles of the Neotropical poison frog Allobates femoralis ( Boulenger, 1884) to test their reaction to cues with two modalities from two different sympatrically occurring potential predators: heterospecific predatory Dendrobates tinctorius tadpoles and dragonfly larvae. We presented A. femoralis tadpoles with olfactory or visual cues, or a combination of the two, and compared their reaction to a water control in a between-individual design. In our trials, A. femoralis tadpoles reacted to multi-modal stimuli (a combination of visual and chemical information) originating from dragonfly larvae with avoidance but showed no reaction to uni-modal cues or cues from heterospecific tadpoles. In addition, visual cues from conspecifics increased swimming activity while cues from predators had no effect on tadpole activity. Our results show that A. femoralis tadpoles can innately recognize some predators and probably need both visual and chemical information to effectively avoid them. This is the first study looking at anti-predator behavior in poison frog tadpoles. We discuss how parental care might influence the expression of predator avoidance responses in tadpoles.

On the dynamic slip boundary condition for Navier-Stokes-like problems - Abbatiello, Anna; Bulíček, Miroslav; Maringová, Erika (Mathematical Models and Methods in Applied Sciences)
The choice of the boundary conditions in mechanical problems has to reflect the interaction of the considered material with the surface. Still the assumption of the no-slip condition is preferred in order to avoid boundary terms in the analysis and slipping effects are usually overlooked. Besides the “static slip models”, there are phenomena that are not accurately described by them, e.g. at the moment when the slip changes rapidly, the wall shear stress and the slip can exhibit a sudden overshoot and subsequent relaxation. When these effects become significant, the so-called dynamic slip phenomenon occurs. We develop a mathematical analysis of Navier–Stokes-like problems with a dynamic slip boundary condition, which requires a proper generalization of the Gelfand triplet and the corresponding function space setting.

The effect of geometry and illumination on appearance perception of different material categories - Chen, Bin; Wang, Chao; Piovarci, Michael; Seidel, Hans Peter; Didyk, Piotr; Myszkowski, Karol; Serrano, Ana (Visual Computer)
The understanding of material appearance perception is a complex problem due to interactions between material reflectance, surface geometry, and illumination. Recently, Serrano et al. collected the largest dataset to date with subjective ratings of material appearance attributes, including glossiness, metallicness, sharpness and contrast of reflections. In this work, we make use of their dataset to investigate for the first time the impact of the interactions between illumination, geometry, and eight different material categories in perceived appearance attributes. After an initial analysis, we select for further analysis the four material categories that cover the largest range for all perceptual attributes: fabric, plastic, ceramic, and metal. Using a cumulative link mixed model (CLMM) for robust regression, we discover interactions between these material categories and four representative illuminations and object geometries. We believe that our findings contribute to expanding the knowledge on material appearance perception and can be useful for many applications, such as scene design, where any particular material in a given shape can be aligned with dominant classes of illumination, so that a desired strength of appearance attributes can be achieved.

Extracellular hyaluronate pressure shaped by cellular tethers drives tissue morphogenesis - Munjal, Akankshi; Hannezo, Edouard B; Tsai, Tony Y.C.; Mitchison, Timothy J.; Megason, Sean G. (Cell)
How tissues acquire complex shapes is a fundamental question in biology and regenerative medicine. Zebrafish semicircular canals form from invaginations in the otic epithelium (buds) that extend and fuse to form the hubs of each canal. We find that conventional actomyosin-driven behaviors are not required. Instead, local secretion of hyaluronan, made by the enzymes uridine 5′-diphosphate dehydrogenase (ugdh) and hyaluronan synthase 3 (has3), drives canal morphogenesis. Charged hyaluronate polymers osmotically swell with water and generate isotropic extracellular pressure to deform the overlying epithelium into buds. The mechanical anisotropy needed to shape buds into tubes is conferred by a polarized distribution of actomyosin and E-cadherin-rich membrane tethers, which we term cytocinches. Most work on tissue morphogenesis ascribes actomyosin contractility as the driving force, while the extracellular matrix shapes tissues through differential stiffness. Our work inverts this expectation. Hyaluronate pressure shaped by anisotropic tissue stiffness may be a widespread mechanism for powering morphological change in organogenesis and tissue engineering.

Determinacy in discrete-bidding infinite-duration games - Aghajohari, Milad; Avni, Guy; Henzinger, Thomas A (Logical Methods in Computer Science)
In two-player games on graphs, the players move a token through a graph to produce an infinite path, which determines the winner of the game. Such games are central in formal methods since they model the interaction between a non-terminating system and its environment. In bidding games the players bid for the right to move the token: in each round, the players simultaneously submit bids, and the higher bidder moves the token and pays the other player. Bidding games are known to have a clean and elegant mathematical structure that relies on the ability of the players to submit arbitrarily small bids. Many applications, however, require a fixed granularity for the bids, which can represent, for example, the monetary value expressed in cents. We study, for the first time, the combination of discrete-bidding and infinite-duration games. Our most important result proves that these games form a large determined subclass of concurrent games, where determinacy is the strong property that there always exists exactly one player who can guarantee winning the game. In particular, we show that, in contrast to non-discrete bidding games, the mechanism with which tied bids are resolved plays an important role in discrete-bidding games. We study several natural tie-breaking mechanisms and show that, while some do not admit determinacy, most natural mechanisms imply determinacy for every pair of initial budgets.
Keywords: computer science; computer science and game theory; logic in computer science

Reverse firewalls for adaptively secure MPC without setup - Chakraborty, Suvradip; Ganesh, Chaya; Pancholi, Mahak; Sarkar, Pratik (27th International Conference on the Theory and Application of Cryptology and Information Security)
We study Multi-party computation (MPC) in the setting of subversion, where the adversary tampers with the machines of honest parties. Our goal is to construct actively secure MPC protocols where parties are corrupted adaptively by an adversary (as in the standard adaptive security setting), and in addition, honest parties’ machines are compromised. The idea of reverse firewalls (RF) was introduced at EUROCRYPT’15 by Mironov and Stephens-Davidowitz as an approach to protecting protocols against corruption of honest parties’ devices. Intuitively, an RF for a party P is an external entity that sits between P and the outside world and whose scope is to sanitize P ’s incoming and outgoing messages in the face of subversion of their computer. Mironov and Stephens-Davidowitz constructed a protocol for passively-secure two-party computation. At CRYPTO’20, Chakraborty, Dziembowski and Nielsen constructed a protocol for secure computation with firewalls that improved on this result, both by extending it to multi-party computation protocol, and considering active security in the presence of static corruptions. In this paper, we initiate the study of RF for MPC in the adaptive setting. We put forward a definition for adaptively secure MPC in the reverse firewall setting, explore relationships among the security notions, and then construct reverse firewalls for MPC in this stronger setting of adaptive security. We also resolve the open question of Chakraborty, Dziembowski and Nielsen by removing the need for a trusted setup in constructing RF for MPC. Towards this end, we construct reverse firewalls for adaptively secure augmented coin tossing and adaptively secure zero-knowledge protocols and obtain a constant round adaptively secure MPC protocol in the reverse firewall setting without setup. Along the way, we propose a new multi-party adaptively secure coin tossing protocol in the plain model, that is of independent interest.

Combined effect of cell geometry and polarity domains determines the orientation of unequal division - Godard, Benoit G; Dumollard, Remi; Heisenberg, Carl-Philipp J; Mcdougall, Alex (eLife)
Cell division orientation is thought to result from a competition between cell geometry and polarity domains controlling the position of the mitotic spindle during mitosis. Depending on the level of cell shape anisotropy or the strength of the polarity domain, one dominates the other and determines the orientation of the spindle. Whether and how such competition is also at work to determine unequal cell division (UCD), producing daughter cells of different size, remains unclear. Here, we show that cell geometry and polarity domains cooperate, rather than compete, in positioning the cleavage plane during UCDs in early ascidian embryos. We found that the UCDs and their orientation at the ascidian third cleavage rely on the spindle tilting in an anisotropic cell shape, and cortical polarity domains exerting different effects on spindle astral microtubules. By systematically varying mitotic cell shape, we could modulate the effect of attractive and repulsive polarity domains and consequently generate predicted daughter cell size asymmetries and position. We therefore propose that the spindle position during UCD is set by the combined activities of cell geometry and polarity domains, where cell geometry modulates the effect of cortical polarity domain(s).

Toll-like receptor 4 deficiency facilitates α-synuclein propagation and neurodegeneration in a mouse model of prodromal Parkinson's disease - Venezia, Serena; Kaufmann, Walter; Wenning, Gregor K.; Stefanova, Nadia (Parkinsonism & Related Disorders)
The evidence linking innate immunity mechanisms and neurodegenerative diseases is growing, but the specific mechanisms are incompletely understood. Experimental data suggest that microglial TLR4 mediates the uptake and clearance of α-synuclein also termed synucleinophagy. The accumulation of misfolded α-synuclein throughout the brain is central to Parkinson's disease (PD). The distribution and progression of the pathology is often attributed to the propagation of α-synuclein. Here, we apply a classical α-synuclein propagation model of prodromal PD in wild type and TLR4 deficient mice to study the role of TLR4 in the progression of the disease. Our data suggest that TLR4 deficiency facilitates the α-synuclein seed spreading associated with reduced lysosomal activity of microglia. Three months after seed inoculation, more pronounced proteinase K-resistant α-synuclein inclusion pathology is observed in mice with TLR4 deficiency. The facilitated propagation of α-synuclein is associated with early loss of dopamine transporter (DAT) signal in the striatum and loss of dopaminergic neurons in substantia nigra pars compacta of TLR4 deficient mice. These new results support TLR4 signaling as a putative target for disease modification to slow the progression of PD and related disorders.

Shadow surface states in topological Kondo insulators - Ghazaryan, Areg; Nica, Emilian M.; Erten, Onur; Ghaemi, Pouyan (New Journal of Physics)
The surface states of 3D topological insulators in general have negligible quantum oscillations (QOs) when the chemical potential is tuned to the Dirac points. In contrast, we find that topological Kondo insulators (TKIs) can support surface states with an arbitrarily large Fermi surface (FS) when the chemical potential is pinned to the Dirac point. We illustrate that these FSs give rise to finite-frequency QOs, which can become comparable to the extremal area of the unhybridized bulk bands. We show that this occurs when the crystal symmetry is lowered from cubic to tetragonal in a minimal two-orbital model. We label such surface modes as 'shadow surface states'. Moreover, we show that the sufficient next-nearest neighbor out-of-plane hybridization leading to shadow surface states can be self-consistently stabilized for tetragonal TKIs. Consequently, shadow surface states provide an important example of high-frequency QOs beyond the context of cubic TKIs.

Excited rotational states of molecules in a superfluid - Cherepanov, Igor; Bighin, Giacomo; Schouder, Constant A.; Chatterley, Adam S.; Albrechtsen, Simon H.; Muñoz, Alberto Viñas; Christiansen, Lars; Stapelfeldt, Henrik; Lemeshko, Mikhail (Physical Review A)
We combine experimental and theoretical approaches to explore excited rotational states of molecules embedded in helium nanodroplets using CS2 and I2 as examples. Laser-induced nonadiabatic molecular alignment is employed to measure spectral lines for rotational states extending beyond those initially populated at the 0.37 K droplet temperature. We construct a simple quantum-mechanical model, based on a linear rotor coupled to a single-mode bosonic bath, to determine the rotational energy structure in its entirety. The calculated and measured spectral lines are in good agreement. We show that the effect of the surrounding superfluid on molecular rotation can be rationalized by a single quantity, the angular momentum, transferred from the molecule to the droplet.

Sparse multi-decoder recursive projection aggregation for Reed-Muller codes - Fathollahi, Dorsa; Farsad, Nariman; Hashemi, Seyyed Ali; Mondelli, Marco (2021 IEEE International Symposium on Information Theory)
We thank Emmanuel Abbe and Min Ye for providing us the implementation of RPA decoding. D. Fathollahi and M. Mondelli are partially supported by the 2019 Lopez-Loreta Prize. N. Farsad is supported by Discovery Grant from the Natural Sciences and Engineering Research Council of Canada (NSERC) and Canada Foundation for Innovation (CFI), John R. Evans Leader Fund. S. A. Hashemi is supported by a Postdoctoral Fellowship from NSERC.

Adversarial training is not ready for robot learning - Lechner, Mathias; Hasani, Ramin; Grosu, Radu; Rus, Daniela; Henzinger, Thomas A (2021 IEEE International Conference on Robotics and Automation)
Adversarial training is an effective method to train deep learning models that are resilient to norm-bounded perturbations, with the cost of nominal performance drop. While adversarial training appears to enhance the robustness and safety of a deep model deployed in open-world decision-critical applications, counterintuitively, it induces undesired behaviors in robot learning settings. In this paper, we show theoretically and experimentally that neural controllers obtained via adversarial training are subjected to three types of defects, namely transient, systematic, and conditional errors. We first generalize adversarial training to a safety-domain optimization scheme allowing for more generic specifications. We then prove that such a learning process tends to cause certain error profiles. We support our theoretical results by a thorough experimental safety analysis in a robot-learning task. Our results suggest that adversarial training is not yet ready for robot learning.

The distribution of the maximum of partial sums of Kloosterman sums and other trace functions - Autissier, Pascal; Bonolis, Dante; Lamzouri, Youness (Compositio Mathematica)
In this paper, we investigate the distribution of the maximum of partial sums of families of m -periodic complex-valued functions satisfying certain conditions. We obtain precise uniform estimates for the distribution function of this maximum in a near-optimal range. Our results apply to partial sums of Kloosterman sums and other families of ℓ -adic trace functions, and are as strong as those obtained by Bober, Goldmakher, Granville and Koukoulopoulos for character sums. In particular, we improve on the recent work of the third author for Birch sums. However, unlike character sums, we are able to construct families of m -periodic complex-valued functions which satisfy our conditions, but for which the Pólya–Vinogradov inequality is sharp.
Keywords: Algebra and Number Theory

Tidying up the mess - Liu, Yu; Ibáñez, Maria (Science)
Thermoelectric materials are engines that convert heat into an electrical current. Intuitively, the efficiency of this process depends on how many electrons (charge carriers) can move and how easily they do so, how much energy those moving electrons transport, and how easily the temperature gradient is maintained. In terms of material properties, an excellent thermoelectric material requires a high electrical conductivity σ, a high Seebeck coefficient S (a measure of the induced thermoelectric voltage as a function of temperature gradient), and a low thermal conductivity κ. The challenge is that these three properties are strongly interrelated in a conflicting manner (1). On page 722 of this issue, Roychowdhury et al. (2) have found a way to partially break these ties in silver antimony telluride (AgSbTe2) with the addition of cadmium (Cd) cations, which increase the ordering in this inherently disordered thermoelectric material.
Keywords: multidisciplinary

Enhanced thermoelectric performance of n-type Bi2Se3 nanosheets through Sn doping - Li, Mengyao; Zhang, Yu; Zhang, Ting; Zuo, Yong; Xiao, Ke; Arbiol, Jordi; Llorca, Jordi; Liu, Yu; Cabot, Andreu (Nanomaterials)
The cost-effective conversion of low-grade heat into electricity using thermoelectric devices requires developing alternative materials and material processing technologies able to reduce the currently high device manufacturing costs. In this direction, thermoelectric materials that do not rely on rare or toxic elements such as tellurium or lead need to be produced using high-throughput technologies not involving high temperatures and long processes. Bi2Se3 is an obvious possible Te-free alternative to Bi2Te3 for ambient temperature thermoelectric applications, but its performance is still low for practical applications, and additional efforts toward finding proper dopants are required. Here, we report a scalable method to produce Bi2Se3 nanosheets at low synthesis temperatures. We studied the influence of different dopants on the thermoelectric properties of this material. Among the elements tested, we demonstrated that Sn doping resulted in the best performance. Sn incorporation resulted in a significant improvement to the Bi2Se3 Seebeck coefficient and a reduction in the thermal conductivity in the direction of the hot-press axis, resulting in an overall 60% improvement in the thermoelectric figure of merit of Bi2Se3.
Keywords: General Materials Science; General Chemical Engineering

Loss of Hem1 disrupts macrophage function and impacts migration, phagocytosis, and integrin-mediated adhesion - Stahnke, Stephanie; Döring, Hermann; Kusch, Charly; de Gorter, David J.J.; Dütting, Sebastian; Guledani, Aleks; Pleines, Irina; Schnoor, Michael; Sixt, Michael K; Geffers, Robert; Rohde, Manfred; Müsken, Mathias; et al. (Current Biology)
Hematopoietic-specific protein 1 (Hem1) is an essential subunit of the WAVE regulatory complex (WRC) in immune cells. WRC is crucial for Arp2/3 complex activation and the protrusion of branched actin filament networks. Moreover, Hem1 loss of function in immune cells causes autoimmune diseases in humans. Here, we show that genetic removal of Hem1 in macrophages diminishes frequency and efficacy of phagocytosis as well as phagocytic cup formation in addition to defects in lamellipodial protrusion and migration. Moreover, Hem1-null macrophages displayed strong defects in cell adhesion despite unaltered podosome formation and concomitant extracellular matrix degradation. Specifically, dynamics of both adhesion and de-adhesion as well as concomitant phosphorylation of paxillin and focal adhesion kinase (FAK) were significantly compromised. Accordingly, disruption of WRC function in non-hematopoietic cells coincided with both defects in adhesion turnover and altered FAK and paxillin phosphorylation. Consistently, platelets exhibited reduced adhesion and diminished integrin αIIbβ3 activation upon WRC removal. Interestingly, adhesion phenotypes, but not lamellipodia formation, were partially rescued by small molecule activation of FAK. A full rescue of the phenotype, including lamellipodia formation, required not only the presence of WRCs but also their binding to and activation by Rac. Collectively, our results uncover that WRC impacts on integrin-dependent processes in a FAK-dependent manner, controlling formation and dismantling of adhesions, relevant for properly grabbing onto extracellular surfaces and particles during cell edge expansion, like in migration or phagocytosis.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Improved deterministic (Δ+1) coloring in low-space MPC - Czumaj, Artur; Davies, Peter; Parter, Merav (Proceedings of the 2021 ACM Symposium on Principles of Distributed Computing)
We present a deterministic O(log log log n)-round low-space Massively Parallel Computation (MPC) algorithm for the classical problem of (Δ+1)-coloring on n-vertex graphs. In this model, every machine has sublinear local space of size n^φ for any arbitrary constant φ \in (0,1). Our algorithm works under the relaxed setting where each machine is allowed to perform exponential local computations, while respecting the n^φ space and bandwidth limitations. Our key technical contribution is a novel derandomization of the ingenious (Δ+1)-coloring local algorithm by Chang-Li-Pettie (STOC 2018, SIAM J. Comput. 2020). The Chang-Li-Pettie algorithm runs in T_local =poly(loglog n) rounds, which sets the state-of-the-art randomized round complexity for the problem in the local model. Our derandomization employs a combination of tools, notably pseudorandom generators (PRG) and bounded-independence hash functions. The achieved round complexity of O(logloglog n) rounds matches the bound of log(T_local ), which currently serves an upper bound barrier for all known randomized algorithms for locally-checkable problems in this model. Furthermore, no deterministic sublogarithmic low-space MPC algorithms for the (Δ+1)-coloring problem have been known before.

On the volume of sections of the cube - Ivanov, Grigory; Tsiutsiurupa, Igor (Analysis and Geometry in Metric Spaces)
We study the properties of the maximal volume k-dimensional sections of the n-dimensional cube [−1, 1]n. We obtain a first order necessary condition for a k-dimensional subspace to be a local maximizer of the volume of such sections, which we formulate in a geometric way. We estimate the length of the projection of a vector of the standard basis of Rn onto a k-dimensional subspace that maximizes the volume of the intersection. We nd the optimal upper bound on the volume of a planar section of the cube [−1, 1]n , n ≥ 2.
Keywords: Applied Mathematics; Geometry and Topology; Analysis

Component stability in low-space massively parallel computation - Czumaj, Artur; Davies, Peter; Parter, Merav (Proceedings of the 2021 ACM Symposium on Principles of Distributed Computing)
In this paper, we study the power and limitations of component-stable algorithms in the low-space model of Massively Parallel Computation (MPC). Recently Ghaffari, Kuhn and Uitto (FOCS 2019) introduced the class of component-stable low-space MPC algorithms, which are, informally, defined as algorithms for which the outputs reported by the nodes in different connected components are required to be independent. This very natural notion was introduced to capture most (if not all) of the known efficient MPC algorithms to date, and it was the first general class of MPC algorithms for which one can show non-trivial conditional lower bounds. In this paper we enhance the framework of component-stable algorithms and investigate its effect on the complexity of randomized and deterministic low-space MPC. Our key contributions include: 1) We revise and formalize the lifting approach of Ghaffari, Kuhn and Uitto. This requires a very delicate amendment of the notion of component stability, which allows us to fill in gaps in the earlier arguments. 2) We also extend the framework to obtain conditional lower bounds for deterministic algorithms and fine-grained lower bounds that depend on the maximum degree Δ. 3) We demonstrate a collection of natural graph problems for which non-component-stable algorithms break the conditional lower bound obtained for component-stable algorithms. This implies that, for both deterministic and randomized algorithms, component-stable algorithms are conditionally weaker than the non-component-stable ones. Altogether our results imply that component-stability might limit the computational power of the low-space MPC model, paving the way for improved upper bounds that escape the conditional lower bound setting of Ghaffari, Kuhn, and Uitto.

Self-adjoint extensions of bipartite Hamiltonians - Lenz, Daniel; Weinmann, Timon; Wirth, Melchior (Proceedings of the Edinburgh Mathematical Society)
We compute the deficiency spaces of operators of the form 𝐻𝐴⊗̂ 𝐼+𝐼⊗̂ 𝐻𝐵, for symmetric 𝐻𝐴 and self-adjoint 𝐻𝐵. This enables us to construct self-adjoint extensions (if they exist) by means of von Neumann's theory. The structure of the deficiency spaces for this case was asserted already in Ibort et al. [Boundary dynamics driven entanglement, J. Phys. A: Math. Theor. 47(38) (2014) 385301], but only proven under the restriction of 𝐻𝐵 having discrete, non-degenerate spectrum.

Correlation energy of a weakly interacting Fermi gas - Benedikter, Niels P; Nam, Phan Thành; Porta, Marcello; Schlein, Benjamin; Seiringer, Robert (Inventiones Mathematicae)
We derive rigorously the leading order of the correlation energy of a Fermi gas in a scaling regime of high density and weak interaction. The result verifies the prediction of the random-phase approximation. Our proof refines the method of collective bosonization in three dimensions. We approximately diagonalize an effective Hamiltonian describing approximately bosonic collective excitations around the Hartree–Fock state, while showing that gapless and non-collective excitations have only a negligible effect on the ground state energy.

Different to the core: The pre-supernova structures of massive single and binary-stripped stars - Laplace, E.; Justham, S.; Renzo, M.; Götberg, Ylva Louise Linsdotter; Farmer, R.; Vartanyan, D.; de Mink, S. E. (Astronomy & Astrophysics)
The majority of massive stars live in binary or multiple systems and will interact with a companion during their lifetimes, which helps to explain the observed diversity of core-collapse supernovae. Donor stars in binary systems can lose most of their hydrogen-rich envelopes through mass transfer. As a result, not only are the surface properties affected, but so is the core structure. However, most calculations of the core-collapse properties of massive stars rely on single-star models. We present a systematic study of the difference between the pre-supernova structures of single stars and stars of the same initial mass (11–21 M⊙) that have been stripped due to stable post-main-sequence mass transfer at solar metallicity. We present the pre-supernova core composition with novel diagrams that give an intuitive representation of the isotope distribution. As shown in previous studies, at the edge of the carbon-oxygen core, the binary-stripped star models contain an extended gradient of carbon, oxygen, and neon. This layer remains until core collapse and is more extended in mass for higher initial stellar masses. It originates from the receding of the convective helium core during core helium burning in binary-stripped stars, which does not occur in single-star models. We find that this same evolutionary phase leads to systematic differences in the final density and nuclear energy generation profiles. Binary-stripped star models have systematically higher total masses of carbon at the moment of core collapse compared to single-star models, which likely results in systematically different supernova yields. In about half of our models, the silicon-burning and oxygen-rich layers merge after core silicon burning. We discuss the implications of our findings for the “explodability”, supernova observations, and nucleosynthesis of these stars. Our models are publicly available and can be readily used as input for detailed supernova simulations.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

On nonlinear problems of parabolic type with implicit constitutive equations involving flux - Bulíček, Miroslav; Maringová, Erika; Málek, Josef (Mathematical Models and Methods in Applied Sciences)
We study systems of nonlinear partial differential equations of parabolic type, in which the elliptic operator is replaced by the first-order divergence operator acting on a flux function, which is related to the spatial gradient of the unknown through an additional implicit equation. This setting, broad enough in terms of applications, significantly expands the paradigm of nonlinear parabolic problems. Formulating four conditions concerning the form of the implicit equation, we first show that these conditions describe a maximal monotone p-coercive graph. We then establish the global-in-time and large-data existence of a (weak) solution and its uniqueness. To this end, we adopt and significantly generalize Minty’s method of monotone mappings. A unified theory, containing several novel tools, is developed in a way to be tractable from the point of view of numerical approximations.
Keywords: Nonlinear parabolic systems; implicit constitutive theory; weak solutions; existence; uniqueness

Brief announcement: Be prepared when network goes bad: An asynchronous view-change protocol - Gelashvili, Rati; Kokoris Kogias, Eleftherios; Spiegelman, Alexander; Xiang, Zhuolun (Proceedings of the 2021 ACM Symposium on Principles of Distributed Computing)
The popularity of permissioned blockchain systems demands BFT SMR protocols that are efficient under good network conditions (synchrony) and robust under bad network conditions (asynchrony). The state-of-the-art partially synchronous BFT SMR protocols provide optimal linear communication cost per decision under synchrony and good leaders, but lose liveness under asynchrony. On the other hand, the state-of-the-art asynchronous BFT SMR protocols are live even under asynchrony, but always pay quadratic cost even under synchrony. In this paper, we propose a BFT SMR protocol that achieves the best of both worlds -- optimal linear cost per decision under good networks and leaders, optimal quadratic cost per decision under bad networks, and remains always live.
Keywords: optimal; state machine replication; fallback; asynchrony; byzantine faults

Entanglement view of dynamical quantum phase transitions - De Nicola, Stefano; Michailidis, Alexios; Serbyn, Maksym (Physical Review Letters)
The analogy between an equilibrium partition function and the return probability in many-body unitary dynamics has led to the concept of dynamical quantum phase transition (DQPT). DQPTs are defined by nonanalyticities in the return amplitude and are present in many models. In some cases, DQPTs can be related to equilibrium concepts, such as order parameters, yet their universal description is an open question. In this Letter, we provide first steps toward a classification of DQPTs by using a matrix product state description of unitary dynamics in the thermodynamic limit. This allows us to distinguish the two limiting cases of “precession” and “entanglement” DQPTs, which are illustrated using an analytical description in the quantum Ising model. While precession DQPTs are characterized by a large entanglement gap and are semiclassical in their nature, entanglement DQPTs occur near avoided crossings in the entanglement spectrum and can be distinguished by a complex pattern of nonlocal correlations. We demonstrate the existence of precession and entanglement DQPTs beyond Ising models, discuss observables that can distinguish them, and relate their interplay to complex DQPT phenomenology.
Keywords: General Physics and Astronomy

mRNA surveillance complex PELOTA-HBS1 eegulates phosphoinositide-sependent protein kinase1 and plant growth - Kong, W; Tan, Shutang; Zhao, Q; Lin, DL; Xu, ZH; Friml, Jiří; Xue, HW (Plant Physiology)
The quality control system for messenger RNA (mRNA) is fundamental for cellular activities in eukaryotes. To elucidate the molecular mechanism of 3'-Phosphoinositide-Dependent Protein Kinase1 (PDK1), a master regulator that is essential throughout eukaryotic growth and development, we employed a forward genetic approach to screen for suppressors of the loss-of-function T-DNA insertion double mutant pdk1.1 pdk1.2 in Arabidopsis thaliana. Notably, the severe growth attenuation of pdk1.1 pdk1.2 was rescued by sop21 (suppressor of pdk1.1 pdk1.2), which harbours a loss-of-function mutation in PELOTA1 (PEL1). PEL1 is a homologue of mammalian PELOTA and yeast (Saccharomyces cerevisiae) DOM34p, which each form a heterodimeric complex with the GTPase HBS1 (HSP70 SUBFAMILY B SUPPRESSOR1, also called SUPERKILLER PROTEIN7, SKI7), a protein that is responsible for ribosomal rescue and thereby assures the quality and fidelity of mRNA molecules during translation. Genetic analysis further revealed that a dysfunctional PEL1-HBS1 complex failed to degrade the T-DNA-disrupted PDK1 transcripts, which were truncated but functional, and thus rescued the growth and developmental defects of pdk1.1 pdk1.2. Our studies demonstrated the functionality of a homologous PELOTA-HBS1 complex and identified its essential regulatory role in plants, providing insights into the mechanism of mRNA quality control.

Tight frames and related geometric problems - Ivanov, Grigory (Canadian Mathematical Bulletin)
A tight frame is the orthogonal projection of some orthonormal basis of Rn onto Rk. We show that a set of vectors is a tight frame if and only if the set of all cross products of these vectors is a tight frame. We reformulate a range of problems on the volume of projections (or sections) of regular polytopes in terms of tight frames and write a first-order necessary condition for local extrema of these problems. As applications, we prove new results for the problem of maximization of the volume of zonotopes.
Keywords: General Mathematics; Tight frame; Grassmannian; zonotope

AGC kinases and MAB4/MEL proteins maintain PIN polarity by limiting lateral diffusion in plant cells - Glanc, Matous; Van Gelderen, K; Hörmayer, Lukas; Tan, Shutang; Naramoto, S; Zhang, Xixi; Domjan, David; Vcelarova, L; Hauschild, Robert; Johnson, Alexander J; de Koning, E; van Dop, M; et al. (Current Biology)
Polar subcellular localization of the PIN exporters of the phytohormone auxin is a key determinant of directional, intercellular auxin transport and thus a central topic of both plant cell and developmental biology. Arabidopsis mutants lacking PID, a kinase that phosphorylates PINs, or the MAB4/MEL proteins of unknown molecular function display PIN polarity defects and phenocopy pin mutants, but mechanistic insights into how these factors convey PIN polarity are missing. Here, by combining protein biochemistry with quantitative live-cell imaging, we demonstrate that PINs, MAB4/MELs, and AGC kinases interact in the same complex at the plasma membrane. MAB4/MELs are recruited to the plasma membrane by the PINs and in concert with the AGC kinases maintain PIN polarity through limiting lateral diffusion-based escape of PINs from the polar domain. The PIN-MAB4/MEL-PID protein complex has self-reinforcing properties thanks to positive feedback between AGC kinase-mediated PIN phosphorylation and MAB4/MEL recruitment. We thus uncover the molecular mechanism by which AGC kinases and MAB4/MEL proteins regulate PIN localization and plant development.